Frequent horizontal chromosome transfer between asexual fungal insect pathogens - Habig, Michael; Grasse, Anna V; Müller, Judith; Stukenbrock, Eva H.; Leitner, Hanna; Cremer, Sylvia (Proceedings of the National Academy of Sciences of the United States of America)
Entire chromosomes are typically only transmitted vertically from one generation to the next. The horizontal transfer of such chromosomes has long been considered improbable, yet gained recent support in several pathogenic fungi where it may affect the fitness or host specificity. To date, it is unknown how these transfers occur, how common they are and whether they can occur between different species. In this study, we show multiple independent instances of horizontal transfers of the same accessory chromosome between two distinct strains of the asexual entomopathogenic fungus Metarhizium robertsii during experimental co-infection of its insect host, the Argentine ant. Notably, only the one chromosome – but no other – was transferred from the donor to the recipient strain. The recipient strain, now harboring the accessory chromosome, exhibited a competitive advantage under certain host conditions. By phylogenetic analysis we further demonstrate that the same accessory chromosome was horizontally transferred in a natural environment between M. robertsii and another congeneric insect pathogen, M. guizhouense . Hence horizontal chromosome transfer is not limited to the observed frequent events within species during experimental infections but also occurs naturally across species. The transferred accessory chromosome contains genes that might be involved in its preferential horizontal transfer, encoding putative histones and histone-modifying enzymes, but also putative virulence factors that may support its establishment. Our study reveals that both intra- and interspecies horizontal transfer of entire chromosomes is more frequent than previously assumed, likely representing a not uncommon mechanism for gene exchange. Significance Statement The enormous success of bacterial pathogens has been attributed to their ability to exchange genetic material between one another. Similarly, in eukaryotes, horizontal transfer of genetic material allowed the spread of virulence factors across species. The horizontal transfer of whole chromosomes could be an important pathway for such exchange of genetic material, but little is known about the origin of transferable chromosomes and how frequently they are exchanged. Here, we show that the transfer of accessory chromosomes - chromosomes that are non-essential but may provide fitness benefits - is common during fungal co-infections and is even possible between distant pathogenic species, highlighting the importance of horizontal gene transfer via chromosome transfer also for the evolution and function of eukaryotic pathogens.

Multiplicative auction algorithm for approximate maximum weight bipartite matching - Zheng, Da Wei; Henzinger, Monika H (Mathematical Programming)
We present an auction algorithm using multiplicative instead of constant weight updates to compute a (1-E)-approximate maximum weight matching (MWM) in a bipartite graph with n vertices and m edges in time 0(mE-1), beating the running time of the fastest known approximation algorithm of Duan and Pettie [JACM ’14] that runs in 0(mE-1 log E-1). Our algorithm is very simple and it can be extended to give a dynamic data structure that maintains a (1-E)-approximate maximum weight matching under (1) one-sided vertex deletions (with incident edges) and (2) one-sided vertex insertions (with incident edges sorted by weight) to the other side. The total time time used is 0(mE-1), where m is the sum of the number of initially existing and inserted edges.

Unravelling the reaction mechanism for H2 production via formic acid decomposition over Pd: Coverage-dependent microkinetic modeling - Yao, Zihao; Liu, Xu; Bunting, Rhys; Wang, Jianguo (Chemical Engineering Science)
As a key liquid organic hydrogen carrier, investigating the decomposition of formic acid (HCOOH) on the Pd (1 1 1) transition metal surface is imperative for harnessing hydrogen energy. Despite a multitude of studies, the major mechanisms and key intermediates involved in the dehydrogenation process of formic acid remain a great topic of debate due to ambiguous adsorbate interactions. In this research, we develop an advanced microkinetic model based on first-principles calculations, accounting for adsorbate–adsorbate interactions. Our study unveils a comprehensive mechanism for the Pd (1 1 1) surface, highlighting the significance of coverage effects in formic acid dehydrogenation. Our findings unequivocally demonstrate that H coverage on the Pd (1 1 1) surface renders formic acid more susceptible to decompose into H2 and CO2 through COOH intermediates. Consistent with experimental results, the selectivity of H2 in the decomposition of formic acid on the Pd (1 1 1) surface approaches 100 %. Considering the influence of H coverage, our kinetic analysis aligns perfectly with experimental values at a temperature of 373 K.

Elucidating the role of water in collagen self-assembly by isotopically modulating collagen hydration - Giubertoni, Giulia; Feng, Liru; Klein, Kevin; Giannetti, Guido; Rutten, Luco; Choi, Yeji; Van Der Net, Anouk; Castro-Linares, Gerard; Caporaletti, Federico; Micha, Dimitra; Hunger, Johannes; Deblais, Antoine; et al. (Proceedings of the National Academy of Sciences of the United States of America)
Water is known to play an important role in collagen self-assembly, but it is still largely unclear how water–collagen interactions influence the assembly process and determine the fibril network properties. Here, we use the H2O/D2O isotope effect on the hydrogen-bond strength in water to investigate the role of hydration in collagen self-assembly. We dissolve collagen in H2O and D2O and compare the growth kinetics and the structure of the collagen assemblies formed in these water isotopomers. Surprisingly, collagen assembly occurs ten times faster in D2O than in H2O, and collagen in D2O self-assembles into much thinner fibrils, that form a more inhomogeneous and softer network, with a fourfold reduction in elastic modulus when compared to H2O. Combining spectroscopic measurements with atomistic simulations, we show that collagen in D2O is less hydrated than in H2O. This partial dehydration lowers the enthalpic penalty for water removal and reorganization at the collagen–water interface, increasing the self-assembly rate and the number of nucleation centers, leading to thinner fibrils and a softer network. Coarse-grained simulations show that the acceleration in the initial nucleation rate can be reproduced by the enhancement of electrostatic interactions. These results show that water acts as a mediator between collagen monomers, by modulating their interactions so as to optimize the assembly process and, thus, the final network properties. We believe that isotopically modulating the hydration of proteins can be a valuable method to investigate the role of water in protein structural dynamics and protein self-assembly.

Structure, biophysics, and circuit function of a "giant" cortical presynaptic terminal - Vandael, David H; Jonas, Peter M (Science)
The hippocampal mossy fiber synapse, formed between axons of dentate gyrus granule cells and dendrites of CA3 pyramidal neurons, is a key synapse in the trisynaptic circuitry of the hippocampus. Because of its comparatively large size, this synapse is accessible to direct presynaptic recording, allowing a rigorous investigation of the biophysical mechanisms of synaptic transmission and plasticity. Furthermore, because of its placement in the very center of the hippocampal memory circuit, this synapse seems to be critically involved in several higher network functions, such as learning, memory, pattern separation, and pattern completion. Recent work based on new technologies in both nanoanatomy and nanophysiology, including presynaptic patch-clamp recording, paired recording, super-resolution light microscopy, and freeze-fracture and “flash-and-freeze” electron microscopy, has provided new insights into the structure, biophysics, and network function of this intriguing synapse. This brings us one step closer to answering a fundamental question in neuroscience: how basic synaptic properties shape higher network computations.

Persistence and Morse theory for discrete geometric structures - Cultrera di Montesano, Sebastiano
Point sets, geometric networks, and arrangements of hyperplanes are fundamental objects in discrete geometry that have captivated mathematicians for centuries, if not millennia. This thesis seeks to cast new light on these structures by illustrating specific instances where a topological perspective, specifically through discrete Morse theory and persistent homology, provides valuable insights. At first glance, the topology of these geometric objects might seem uneventful: point sets essentially lack of topology, arrangements of hyperplanes are a decomposition of Rd, which is a contractible space, and the topology of a network primarily involves the enumeration of connected components and cycles within the network. However, beneath this apparent simplicity, there lies an array of intriguing structures, a small subset of which will be uncovered in this thesis. Focused on three case studies, each addressing one of the mentioned objects, this work will showcase connections that intertwine topology with diverse fields such as combinatorial geometry, algorithms and data structures, and emerging applications like spatial biology.

Dynamically maintaining the persistent homology of time series - Cultrera di Montesano, Sebastiano; Edelsbrunner, Herbert; Henzinger, Monika H; Ost, Lara (Proceedings of the 2024 Annual ACM-SIAM Symposium on Discrete Algorithms (SODA))
We present a dynamic data structure for maintaining the persistent homology of a time series of real numbers. The data structure supports local operations, including the insertion and deletion of an item and the cutting and concatenating of lists, each in time O(log n + k), in which n counts the critical items and k the changes in the augmented persistence diagram. To achieve this, we design a tailor-made tree structure with an unconventional representation, referred to as banana tree, which may be useful in its own right.

Chromatic alpha complexes - Cultrera di Montesano, Sebastiano; Draganov, Ondrej; Edelsbrunner, Herbert; Saghafian, Morteza (arXiv)
Motivated by applications in the medical sciences, we study finite chromatic sets in Euclidean space from a topological perspective. Based on the persistent homology for images, kernels and cokernels, we design provably stable homological quantifiers that describe the geometric micro- and macro-structure of how the color classes mingle. These can be efficiently computed using chromatic variants of Delaunay and alpha complexes, and code that does these computations is provided.

Co-dependent excitatory and inhibitory plasticity accounts for quick, stable and long-lasting memories in biological networks - Agnes, Everton J.; Vogels, Tim P (Nature Neuroscience)
The brain’s functionality is developed and maintained through synaptic plasticity. As synapses undergo plasticity, they also affect each other. The nature of such ‘co-dependency’ is difficult to disentangle experimentally, because multiple synapses must be monitored simultaneously. To help understand the experimentally observed phenomena, we introduce a framework that formalizes synaptic co-dependency between different connection types. The resulting model explains how inhibition can gate excitatory plasticity while neighboring excitatory–excitatory interactions determine the strength of long-term potentiation. Furthermore, we show how the interplay between excitatory and inhibitory synapses can account for the quick rise and long-term stability of a variety of synaptic weight profiles, such as orientation tuning and dendritic clustering of co-active synapses. In recurrent neuronal networks, co-dependent plasticity produces rich and stable motor cortex-like dynamics with high input sensitivity. Our results suggest an essential role for the neighborly synaptic interaction during learning, connecting micro-level physiology with network-wide phenomena.

Concentration without independence via information measures - Esposito, Amedeo Roberto; Mondelli, Marco (IEEE Transactions on Information Theory)
We propose a novel approach to concentration for non-independent random variables. The main idea is to “pretend” that the random variables are independent and pay a multiplicative price measuring how far they are from actually being independent. This price is encapsulated in the Hellinger integral between the joint and the product of the marginals, which is then upper bounded leveraging tensorisation properties. Our bounds represent a natural generalisation of concentration inequalities in the presence of dependence: we recover exactly the classical bounds (McDiarmid’s inequality) when the random variables are independent. Furthermore, in a “large deviations” regime, we obtain the same decay in the probability as for the independent case, even when the random variables display non-trivial dependencies. To show this, we consider a number of applications of interest. First, we provide a bound for Markov chains with finite state space. Then, we consider the Simple Symmetric Random Walk, which is a non-contracting Markov chain, and a non-Markovian setting in which the stochastic process depends on its entire past. To conclude, we propose an application to Markov Chain Monte Carlo methods, where our approach leads to an improved lower bound on the minimum burn-in period required to reach a certain accuracy. In all of these settings, we provide a regime of parameters in which our bound fares better than what the state of the art can provide.

UNCOVER spectroscopy confirms the surprising ubiquity of active galactic nuclei in red sources at z > 5 - Greene, Jenny E.; Labbe, Ivo; Goulding, Andy D.; Furtak, Lukas J.; Chemerynska, Iryna; Kokorev, Vasily; Dayal, Pratika; Volonteri, Marta; Williams, Christina C.; Wang, Bingjie; Setton, David J.; Burgasser, Adam J.; et al. (Astrophysical Journal)
The James Webb Space Telescope is revealing a new population of dust-reddened broad-line active galactic nuclei (AGN) at redshifts z ≳ 5. Here we present deep NIRSpec/Prism spectroscopy from the Cycle 1 Treasury program Ultradeep NIRSpec and NIRCam ObserVations before the Epoch of Reionization (UNCOVER) of 15 AGN candidates selected to be compact, with red continua in the rest-frame optical but with blue slopes in the UV. From NIRCam photometry alone, they could have been dominated by dusty star formation or an AGN. Here we show that the majority of the compact red sources in UNCOVER are dust-reddened AGN: 60% show definitive evidence for broad-line Hα with a FWHM > 2000 km s −1, 20% of the current data are inconclusive, and 20% are brown dwarf stars. We propose an updated photometric criterion to select red z > 5 AGN that excludes brown dwarfs and is expected to yield >80% AGN. Remarkably, among all zphot > 5 galaxies with F277W – F444W > 1 in UNCOVER at least 33% are AGN regardless of compactness, climbing to at least 80% AGN for sources with F277W – F444W > 1.6. The confirmed AGN have black hole masses of 107–109M⊙. While their UV luminosities (−16 > MUV > −20 AB mag) are low compared to UV-selected AGN at these epochs, consistent with percent-level scattered AGN light or low levels of unobscured star formation, the inferred bolometric luminosities are typical of 107–109M⊙ black holes radiating at ∼10%–40% the Eddington limit. The number densities are surprisingly high at ∼10−5 Mpc−3 mag−1, 100 times more common than the faintest UV-selected quasars, while accounting for ∼1% of the UV-selected galaxies. While their UV faintness suggests they may not contribute strongly to reionization, their ubiquity poses challenges to models of black hole growth.

Hardness of linearly ordered 4-colouring of 3-colourable 3-uniform hypergraphs - Filakovský, Marek; Nakajima, Tamio Vesa; Opršal, Jakub; Tasinato, Gianluca; Wagner, Uli (41st International Symposium on Theoretical Aspects of Computer Science)
A linearly ordered (LO) k-colouring of a hypergraph is a colouring of its vertices with colours 1, … , k such that each edge contains a unique maximal colour. Deciding whether an input hypergraph admits LO k-colouring with a fixed number of colours is NP-complete (and in the special case of graphs, LO colouring coincides with the usual graph colouring). Here, we investigate the complexity of approximating the "linearly ordered chromatic number" of a hypergraph. We prove that the following promise problem is NP-complete: Given a 3-uniform hypergraph, distinguish between the case that it is LO 3-colourable, and the case that it is not even LO 4-colourable. We prove this result by a combination of algebraic, topological, and combinatorial methods, building on and extending a topological approach for studying approximate graph colouring introduced by Krokhin, Opršal, Wrochna, and Živný (2023).

kCSD-python, reliable current source density estimation with quality control - Chintaluri, Chaitanya; Bejtka, Marta; Sredniawa, Wladyslaw; Czerwinski, Michal; Dzik, Jakub M.; Jedrzejewska-Szmek, Joanna; Wojciki, Daniel K. (PLoS Computational Biology)
Interpretation of extracellular recordings can be challenging due to the long range of electric field. This challenge can be mitigated by estimating the current source density (CSD). Here we introduce kCSD-python, an open Python package implementing Kernel Current Source Density (kCSD) method and related tools to facilitate CSD analysis of experimental data and the interpretation of results. We show how to counter the limitations imposed by noise and assumptions in the method itself. kCSD-python allows CSD estimation for an arbitrary distribution of electrodes in 1D, 2D, and 3D, assuming distributions of sources in tissue, a slice, or in a single cell, and includes a range of diagnostic aids. We demonstrate its features in a Jupyter Notebook tutorial which illustrates a typical analytical workflow and main functionalities useful in validating analysis results.

Exploring beyond-mean-field logarithmic divergences in Fermi-polaron energy - Al Hyder, Ragheed; Chevy, F.; Leyronas, X. (Physical Review A)
We perform a diagrammatic analysis of the energy of a mobile impurity immersed in a strongly interacting two-component Fermi gas to second order in the impurity-bath interaction. These corrections demonstrate divergent behavior in the limit of large impurity momentum. We show the fundamental processes responsible for these logarithmically divergent terms. We study the problem in the general case without any assumptions regarding the fermion-fermion interactions in the bath. We show that the divergent term can be summed up to all orders in the Fermi-Fermi interaction and that the resulting expression is equivalent to the one obtained in the few-body calculation. Finally, we provide a perturbative calculation to the second order in the Fermi-Fermi interaction, and we show the diagrams responsible for these terms.

Decompositions into two linear forests of bounded lengths - Campbell, Rutger; Hörsch, Florian; Moore, Benjamin (Discrete Mathematics)
For some k∈Z≥0∪{∞}, we call a linear forest k-bounded if each of its components has at most k edges. We will say a (k,ℓ)-bounded linear forest decomposition of a graph G is a partition of E(G) into the edge sets of two linear forests Fk,Fℓ where Fk is k-bounded and Fℓ is ℓ-bounded. We show that the problem of deciding whether a given graph has such a decomposition is NP-complete if both k and ℓ are at least 2, NP-complete if k≥9 and ℓ=1, and is in P for (k,ℓ)=(2,1). Before this, the only known NP-complete cases were the (2,2) and (3,3) cases. Our hardness result answers a question of Bermond et al. from 1984. We also show that planar graphs of girth at least nine decompose into a linear forest and a matching, which in particular is stronger than 3-edge-colouring such graphs.

Little Red Dots: An abundant population of faint active galactic nuclei at z ∼ 5 revealed by the EIGER and FRESCO JWST surveys - Matthee, Jorryt J; Naidu, Rohan P.; Brammer, Gabriel; Chisholm, John; Eilers, Anna-Christina; Goulding, Andy; Greene, Jenny; Kashino, Daichi; Labbe, Ivo; Lilly, Simon J.; Mackenzie, Ruari; Oesch, Pascal A.; et al. (The Astrophysical Journal)
Characterizing the prevalence and properties of faint active galactic nuclei (AGNs) in the early Universe is key for understanding the formation of supermassive black holes (SMBHs) and determining their role in cosmic reionization. We perform a spectroscopic search for broad Hα emitters at z ≈ 4–6 using deep JWST/NIRCam imaging and wide field slitless spectroscopy from the EIGER and FRESCO surveys. We identify 20 Hα lines at z = 4.2–5.5 that have broad components with line widths from ∼1200–3700 km s−1, contributing ∼30%–90% of the total line flux. We interpret these broad components as being powered by accretion onto SMBHs with implied masses ∼107–8M⊙. In the UV luminosity range MUV,AGN+host = −21 to −18, we measure number densities of ≈10−5 cMpc−3. This is an order of magnitude higher than expected from extrapolating quasar UV luminosity functions (LFs). Yet, such AGN are found in only <1% of star-forming galaxies at z ∼ 5. The number density discrepancy is much lower when compared to the broad Hα LF. The SMBH mass function agrees with large cosmological simulations. In two objects, we detect complex Hα profiles that we tentatively interpret as caused by absorption signatures from dense gas fueling SMBH growth and outflows. We may be witnessing early AGN feedback that will clear dust-free pathways through which more massive blue quasars are seen. We uncover a strong correlation between reddening and the fraction of total galaxy luminosity arising from faint AGN. This implies that early SMBH growth is highly obscured and that faint AGN are only minor contributors to cosmic reionization.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

A hybrid pathway for self-sustained luminescence - Palkina, Kseniia A.; Karataeva, Tatiana A.; Perfilov, Maxim M.; Fakhranurova, Liliia I.; Markina, Nadezhda M.; Gonzalez Somermeyer, Louisa; Garcia-Perez, Elena; Vazquez-Vilar, Marta; Rodriguez-Rodriguez, Marta; Vazquez-Vilriales, Victor; Shakhova, Ekaterina S.; Mitiouchkina, Tatiana; et al. (Science Advances)
The fungal bioluminescence pathway can be reconstituted in other organisms allowing luminescence imaging without exogenously supplied substrate. The pathway starts from hispidin biosynthesis—a step catalyzed by a large fungal polyketide synthase that requires a posttranslational modification for activity. Here, we report identification of alternative compact hispidin synthases encoded by a phylogenetically diverse group of plants. A hybrid bioluminescence pathway that combines plant and fungal genes is more compact, not dependent on availability of machinery for posttranslational modifications, and confers autonomous bioluminescence in yeast, mammalian, and plant hosts. The compact size of plant hispidin synthases enables additional modes of delivery of autoluminescence, such as delivery with viral vectors.

The unreasonable efficiency of total rain evaporation removal in triggering convective self‐aggregation - Hwong, Yi-Ling; Muller, Caroline J (Geophysical Research Letters)
The elimination of rain evaporation in the planetary boundary layer (PBL) has been found to lead to convective self‐aggregation (CSA) even without radiative feedback, but the precise mechanisms underlying this phenomenon remain unclear. We conducted cloud‐resolving simulations with two domain sizes and progressively reduced rain evaporation in the PBL. Surprisingly, CSA only occurred when rain evaporation was almost completely removed. The additional convective heating resulting from the reduction of evaporative cooling in the moist patch was found to be the trigger, thereafter a dry subsidence intrusion into the PBL in the dry patch takes over and sets CSA in motion. Temperature and moisture anomalies oppose each other in their buoyancy effects, hence explaining the need for almost total rain evaporation removal. We also found radiative cooling and not cold pools to be the leading cause for the comparative ease of CSA to take place in the larger domain.
Keywords: General Earth and Planetary Sciences; Geophysics

Synthetic dimension-induced pseudo Jahn-Teller effect in one-dimensional confined fermions - Becker, A.; Koutentakis, Georgios; Schmelcher, P. (Physical Review Research)
We demonstrate the failure of the adiabatic Born-Oppenheimer approximation to describe the ground state of a quantum impurity within an ultracold Fermi gas despite substantial mass differences between the bath and impurity species. Increasing repulsion leads to the appearance of nonadiabatic couplings between the fast bath and slow impurity degrees of freedom, which reduce the parity symmetry of the latter according to the pseudo Jahn-Teller effect. The presence of this mechanism is associated to a conical intersection involving the impurity position and the inverse of the interaction strength, which acts as a synthetic dimension. We elucidate the presence of these effects via a detailed ground-state analysis involving the comparison of ab initio fully correlated simulations with effective models. Our study suggests ultracold atomic ensembles as potent emulators of complex molecular phenomena.

A route to high thermoelectric performance: Solution‐based control of microstructure and composition in Ag2Se - Kleinhanns, Tobias; Milillo, Francesco; Calcabrini, Mariano; Fiedler, Christine; Horta, Sharona; Balazs, Daniel; Strumolo, Marissa J.; Hasler, Roger; Llorca, Jordi; Tkadletz, Michael; Brutchey, Richard L.; Ibáñez, Maria (Advanced Energy Materials)
Thermoelectric materials convert heat into electricity, with a broad range of applications near room temperature (RT). However, the library of RT high-performance materials is limited. Traditional high-temperature synthetic methods constrain the range of materials achievable, hindering the ability to surpass crystal structure limitations and engineer defects. Here, a solution-based synthetic approach is introduced, enabling RT synthesis of powders and exploration of densification at lower temperatures to influence the material's microstructure. The approach is exemplified by Ag2Se, an n-type alternative to bismuth telluride. It is demonstrated that the concentration of Ag interstitials, grain boundaries, and dislocations are directly correlated to the sintering temperature, and achieve a figure of merit of 1.1 from RT to 100 °C after optimization. Moreover, insights into and resolve Ag2Se's challenges are provided, including stoichiometry issues leading to irreproducible performances. This work highlights the potential of RT solution synthesis in expanding the repertoire of high-performance thermoelectric materials for practical applications.

A pre-monsoon signal of false alarms of Indian monsoon droughts - Goswami, Bidyut B (Geophysical Research Letters)
Current knowledge suggests a drought Indian monsoon (perhaps a severe one) when the El Nino Southern Oscillation and Pacific Decadal Oscillation each exhibit positive phases (a joint positive phase). For the monsoons, which are exceptions in this regard, we found northeast India often gets excess pre-monsoon rainfall. Further investigation reveals that this excess pre-monsoon rainfall is produced by the interaction of the large-scale circulation associated with the joint phase with the mountains in northeast India. We posit that a warmer troposphere, a consequence of excess rainfall over northeast India, drives a stronger monsoon circulation and enhances monsoon rainfall over central India. Hence, we argue that pre-monsoon rainfall over northeast India can be used for seasonal monsoon rainfall prediction over central India. Most importantly, its predictive value is at its peak when the Pacific Ocean exhibits a joint positive phase and the threat of extreme drought monsoon looms over India.

Electron highways are cooler - Navita, Navita; Ibáñez, Maria (Science)
Reducing defects boosts room-temperature performance of a thermoelectric device

Lift-out cryo-FIBSEM and cryo-ET reveal the ultrastructural landscape of extracellular matrix - Zens, Bettina; Fäßler, Florian; Hansen, Jesse; Hauschild, Robert; Datler, Julia; Hodirnau, Victor-Valentin; Zheden, Vanessa; Alanko, Jonna H; Sixt, Michael K; Schur, Florian KM (Journal of Cell Biology)
The extracellular matrix (ECM) serves as a scaffold for cells and plays an essential role in regulating numerous cellular processes, including cell migration and proliferation. Due to limitations in specimen preparation for conventional room-temperature electron microscopy, we lack structural knowledge on how ECM components are secreted, remodeled, and interact with surrounding cells. We have developed a 3D-ECM platform compatible with sample thinning by cryo-focused ion beam milling, the lift-out extraction procedure, and cryo-electron tomography. Our workflow implements cell-derived matrices (CDMs) grown on EM grids, resulting in a versatile tool closely mimicking ECM environments. This allows us to visualize ECM for the first time in its hydrated, native context. Our data reveal an intricate network of extracellular fibers, their positioning relative to matrix-secreting cells, and previously unresolved structural entities. Our workflow and results add to the structural atlas of the ECM, providing novel insights into its secretion and assembly.

Ground state energy of the dilute spin-polarized Fermi gas: Upper bound via cluster expansion - Lauritsen, Asbjørn Bækgaard; Seiringer, Robert (Journal of Functional Analysis)
We prove an upper bound on the ground state energy of the dilute spin-polarized Fermi gas capturing the leading correction to the kinetic energy resulting from repulsive interactions. One of the main ingredients in the proof is a rigorous implementation of the fermionic cluster expansion of Gaudin et al. (1971) [15].

A unifying framework for differentially private sums under continual observation - Henzinger, Monika H; Upadhyay, Jalaj; Upadhyay, Sarvagya (Proceedings of the 2024 Annual ACM-SIAM Symposium on Discrete Algorithms)
We study the problem of maintaining a differentially private decaying sum under continual observation. We give a unifying framework and an efficient algorithm for this problem for any sufficiently smooth function. Our algorithm is the first differentially private algorithm that does not have a multiplicative error for polynomially decaying weights. Our algorithm improves on all prior works on differentially private decaying sums under continual observation and recovers exactly the additive error for the special case of continual counting from Henzinger et al. (SODA 2023) as a corollary. Our algorithm is a variant of the matrix mechanism whose error depends on the γ2 and γF norm of the underlying matrix. We give a constructive proof for an almost exact upper bound on the γ2 and γF norm and an almost tight lower bound on the γ2 norm for a large class of lower-triangular matrices. This is the first non-trivial lower bound for lower-triangular matrices whose non-zero entries are not all the same. It includes matrices for all continual decaying sums problems, resulting in an upper bound on the additive error of any differentially private decaying sums algorithm under continual observation. We also explore some implications of our result in discrepancy theory and operator algebra. Given the importance of the γ2 norm in computer science and the extensive work in mathematics, we believe our result will have further applications.

Large-scale excess H I absorption around z ≈ 4 galaxies detected in a background galaxy spectrum in the MUSE eXtremely deep field - Matthee, Jorryt J; Golling, Christopher; Mackenzie, Ruari; Pezzulli, Gabriele; Lilly, Simon; Schaye, Joop; Bacon, Roland; Kusakabe, Haruka; Urrutia, Tanya; Boogaard, Leindert; Brinchmann, Jarle; Maseda, Michael V.; et al. (Monthly Notices of the Royal Astronomical Society)
Observationally mapping the relation between galaxies and the intergalactic medium (IGM) is of key interest for studies of cosmic reionization. Diffuse hydrogen gas has typically been observed in H I Lyman-α (Lyα) absorption in the spectra of bright background quasars. However, it is important to extend these measurements to background galaxies as quasars become increasingly rare at high redshift and rarely probe closely separated sight lines. Here, we use deep integral field spectroscopy in the MUSE eXtremely Deep Field to demonstrate the measurement of the Lyα transmission at z ≈ 4 in absorption to a background galaxy at z = 4.77. The H I transmission is consistent with independent quasar sight lines at similar redshifts. Exploiting the high number of spectroscopic redshifts of faint galaxies (500 between z = 4.0–4.7 within a radius of 8 arcmin) that are tracers of the density field, we show that Lyα transmission is inversely correlated with galaxy density, i.e. transparent regions in the Lyα forest mark underdense regions at z ≈ 4. Due to large-scale clustering, galaxies are surrounded by excess H I absorption over the cosmic mean out to 4 cMpc/h70. We also find that redshifts from the peak of the Lyα line are typically offset from the systemic redshift by +170 km s−1. This work extends results from z ≈ 2–3 to higher redshifts and demonstrates the power of deep integral field spectroscopy to simultaneously measure the ionization structure of the IGM and the large-scale density field in the early Universe.

Orphan lysosomal solute carrier MFSD1 facilitates highly selective dipeptide transport - Boytsov, Danila; Madej, Gregor M.; Horn, Georg; Blaha, Nadine; Köcher, Thomas; Sitte, Harald H.; Siekhaus, Daria E; Ziegler, Christine; Sandtner, Walter; Roblek, Marko (Proceedings of the National Academy of Sciences of the United States of America)
Orphan solute carrier (SLC) represents a group of membrane transporters whose exact functions and substrate specificities are not known. Elucidating the function and regulation of orphan SLC transporters is not only crucial for advancing our knowledge of cellular and molecular biology but can potentially lead to the development of new therapeutic strategies. Here, we provide evidence for the biological function of a ubiquitous orphan lysosomal SLC, the Major Facilitator Superfamily Domain-containing Protein 1 (MFSD1), which has remained phylogenetically unassigned. Targeted metabolomics revealed that dipeptides containing either lysine or arginine residues accumulate in lysosomes of cells lacking MFSD1. Whole-cell patch-clamp electrophysiological recordings of HEK293-cells expressing MFSD1 on the cell surface displayed transport affinities for positively charged dipeptides in the lower mM range, while dipeptides that carry a negative net charge were not transported. This was also true for single amino acids and tripeptides, which MFSD1 failed to transport. Our results identify MFSD1 as a highly selective lysosomal lysine/arginine/histidine-containing dipeptide exporter, which functions as a uniporter.

Structure and function of the Arabidopsis ABC transporter ABCB19 in brassinosteroid export - Ying, Wei; Wang, Yaowei; Wei, Hong; Luo, Yongming; Ma, Qian; Zhu, Heyuan; Janssens, Hilde; Vukašinović, Nemanja; Kvasnica, Miroslav; Winne, Johan M.; Gao, Yongxiang; Tan, Shutang; et al. (Science)
Brassinosteroids are steroidal phytohormones that regulate plant development and physiology, including adaptation to environmental stresses. Brassinosteroids are synthesized in the cell interior but bind receptors at the cell surface, necessitating a yet to be identified export mechanism. Here, we show that a member of the ATP-binding cassette (ABC) transporter superfamily, ABCB19, functions as a brassinosteroid exporter. We present its structure in both the substrate-unbound and the brassinosteroid-bound states. Bioactive brassinosteroids are potent activators of ABCB19 ATP hydrolysis activity, and transport assays showed that ABCB19 transports brassinosteroids. In Arabidopsis thaliana, ABCB19 and its close homolog, ABCB1, positively regulate brassinosteroid responses. Our results uncover an elusive export mechanism for bioactive brassinosteroids that is tightly coordinated with brassinosteroid signaling.

Mirror symmetry for parabolic Higgs bundles via p-adic integration - Shen, Shiyu (Advances in Mathematics)
Applying the technique of p-adic integration, we prove the topological mirror symmetry conjecture of Hausel-Thaddeus for the moduli spaces of (strongly) parabolic Higgs bundles for the structure groups SLn and PGLn, building on previous work of Groechenig-Wyss-Ziegler on the non-parabolic case. We also prove the E-polynomial of the smooth moduli space of parabolic GLn-Higgs bundles is independent of the degree of the underlying vector bundles.

Odd-sunflowers - Frankl, Peter; Pach, János; Pálvölgyi, Dömötör (Journal of Combinatorial Theory, Series A)
Extending the notion of sunflowers, we call a family of at least two sets an odd-sunflower if every element of the underlying set is contained in an odd number of sets or in none of them. It follows from the Erdős–Szemerédi conjecture, recently proved by Naslund and Sawin, that there is a constant <2 such that every family of subsets of an n-element set that contains no odd-sunflower consists of at most n sets. We construct such families of size at least 1.5021n. We also characterize minimal odd-sunflowers of triples.

A characterization of maps of bounded compression - Dello Schiavo, Lorenzo (Mathematical Communications)
A measurable map between measure spaces is shown to have bounded compression if and only if its image via the measure-algebra functor is Lipschitz-continuous w.r.t. the measure-algebra distances. This provides a natural interpretation of maps of bounded compression/deformation by means of the measure-algebra functor and corrobo-rates the assertion that maps of bounded deformation are a natural class of morphisms for the category of complete and separable metric measure spaces.

Rapid translocation of NGR proteins driving polarization of PIN-activating D6 protein kinase during root gravitropism - Kulich, Ivan; Schmid, Julia; Teplova, Anastasiia; Qi, Linlin; Friml, Jiří (eLife)
Root gravitropic bending represents a fundamental aspect of terrestrial plant physiology. Gravity is perceived by sedimentation of starch-rich plastids (statoliths) to the bottom of the central root cap cells. Following gravity perception, intercellular auxin transport is redirected downwards leading to an asymmetric auxin accumulation at the lower root side causing inhibition of cell expansion, ultimately resulting in downwards bending. How gravity-induced statoliths repositioning is translated into asymmetric auxin distribution remains unclear despite PIN auxin efflux carriers and the Negative Gravitropic Response of roots (NGR) proteins polarize along statolith sedimentation, thus providing a plausible mechanism for auxin flow redirection. In this study, using a functional NGR1-GFP construct, we visualized the NGR1 localization on the statolith surface and plasma membrane (PM) domains in close proximity to the statoliths, correlating with their movements. We determined that NGR1 binding to these PM domains is indispensable for NGR1 functionality and relies on cysteine acylation and adjacent polybasic regions as well as on lipid and sterol PM composition. Detailed timing of the early events following graviperception suggested that both NGR1 repolarization and initial auxin asymmetry precede the visible PIN3 polarization. This discrepancy motivated us to unveil a rapid, NGR-dependent translocation of PIN-activating AGCVIII kinase D6PK towards lower PMs of gravity-perceiving cells, thus providing an attractive model for rapid redirection of auxin fluxes following gravistimulation.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

Ten simple rules for pushing boundaries of inclusion at academic events - Hall, Siobhan Mackenzie; Kochin, Daniel; Carne, Carmel; Herterich, Patricia; Lewers, Kristen Lenay; Abdelhack, Mohamed; Ramasubramanian, Arun; Michael Alphonse, Juno Felecia; Ung, Visotheary; El-Gebali, Sara; Currin, Christopher; Plomp, Esther; et al. (PLOS Computational Biology)
Inclusion at academic events is facing increased scrutiny as the communities these events serve raise their expectations for who can practically attend. Active efforts in recent years to bring more diversity to academic events have brought progress and created momentum. However, we must reflect on these efforts and determine which underrepresented groups are being disadvantaged. Inclusion at academic events is important to ensure diversity of discourse and opinion, to help build networks, and to avoid academic siloing. All of these contribute to the development of a robust and resilient academic field. We have developed these Ten Simple Rules both to amplify the voices that have been speaking out and to celebrate the progress of many Equity, Diversity, and Inclusivity practices that continue to drive the organisation of academic events. The Rules aim to raise awareness as well as provide actionable suggestions and tools to support these initiatives further. This aims to support academic organisations such as the Deep Learning Indaba, Neuromatch Academy, the IBRO-Simons Computational Neuroscience Imbizo, Biodiversity Information Standards (TDWG), Arabs in Neuroscience, FAIRPoints, and OLS (formerly Open Life Science). This article is a call to action for organisers to reevaluate the impact and reach of their inclusive practices.

Land surface modeling informed by earth observation data: Toward understanding blue–green–white water fluxes in High Mountain Asia - Buri, Pascal; Fatichi, Simone; Shaw, Thomas; Fyffe, Catriona Louise; Miles, Evan S.; Mccarthy, Michael; Kneib, Marin; Ren, Shaoting; Jouberton, Achille; Fugger, Stefan; Jia, Li; Zhang, Jing; et al. (Geo-Spatial Information Science)
Mountains are important suppliers of freshwater to downstream areas, affecting large populations in particular in High Mountain Asia (HMA). Yet, the propagation of water from HMA headwaters to downstream areas is not fully understood, as interactions in the mountain water cycle between the cryo-, hydro- and biosphere remain elusive. We review the definition of blue and green water fluxes as liquid water that contributes to runoff at the outlet of the selected domain (blue) and water lost to the atmosphere through vapor fluxes, that is evaporation from water, ground, and interception plus transpiration (green) and propose to add the term white water to account for the (often neglected) evaporation and sublimation from snow and ice. We provide an assessment of models that can simulate the cryo-hydro-biosphere continuum and the interactions between spheres in high mountain catchments, going beyond disciplinary separations. Land surface models are uniquely able to account for such complexity, since they solve the coupled fluxes of water, energy, and carbon between the land surface and atmosphere. Due to the mechanistic nature of such models, specific variables can be compared systematically to independent remote sensing observations – providing vital insights into model accuracy and enabling the understanding of the complex watersheds of HMA. We discuss recent developments in spaceborne earth observation products that have the potential to support catchment modeling in high mountain regions. We then present a pilot study application of the mechanistic land surface model Tethys & Chloris to a glacierized watershed in the Nepalese Himalayas and discuss the use of high-resolution earth observation data to constrain the meteorological forcing uncertainty and validate model results. We use these insights to highlight the remaining challenges and future opportunities that remote sensing data presents for land surface modeling in HMA.

Meta-analysis of the comparative efficacy of benzodiazepines and antidepressants for psychic versus somatic symptoms of generalized anxiety disorder - Beyer, Chad; Currin, Christopher; Williams, Taryn; Stein, Dan J. (Comprehensive Psychiatry)
Background: Benzodiazepines and antidepressants are effective agents for the treatment of generalized anxiety disorder (GAD), with the HAM-A frequently used as a primary outcome measure. The GAD literature is inconsistent regarding which medications are more effective for somatic versus psychic symptoms of GAD, and treatment guidelines do not advocate for prescribing based on subtype. This meta-analysis aimed to determine whether benzodiazepines and antidepressants have a differential impact on the somatic versus psychic subscales of the HAM-A in GAD. Methods: An electronic search was undertaken for randomized controlled trials of either benzodiazepines or antidepressants for GAD that reported treatment response using the HAM-A subscales. Data were extracted by independent reviewers. A random effects assessment of weighted mean difference with 95% confidence intervals and subgroup difference was applied. All analysis was done on SPSS 26. An assessment of bias, and of quality of evidence was performed. Results: 24 randomized controlled trials met the inclusion criteria: 18 antidepressant trials, 5 benzodiazepine trials and 1 of both. 14 studies were assessed as having between some and high risk of bias, while 10 were assessed as having low risk of bias. Benzodiazepines (WMD of 1.81 [CI 1.03, 2.58]) were significantly more effective than antidepressants (WMD of 0.83 [CI 0.64, 1.02]) for reducing somatic symptoms of GAD (Chi2 = 5.81, p = 0.02), and were also more effective (WMD of 2.46 [CI 1.83, 3.09]) in reducing psychic symptoms than antidepressants (WMD of 1.83 [CI 1.55, 2.10]), although this comparison did not reach statistical significance (Chi2 = 3.31, p = 0.07). Conclusion: The finding that benzodiazepines were significantly more effective than antidepressants for somatic symptoms needs to be weighed up against potential benefits of antidepressants over benzodiazepines. It may be useful for future treatment guidelines for GAD to explicitly consider symptom subtype.

A constructive algorithm for building rectifiable curves in weakly convex sets - Lopushanski, Mariana; Ivanov, Grigory (AIP Conference Proceedings)
In this paper we build a constructive algorithm that returns a rectifiable curve that connects two points in a weakly convex set in a Hilbert space. We have proven that this algorithm converges and obtained an estimate on the curve’s length and compare the length of the curve obtained to known results.

Amplifiers of selection for the Moran process with both Birth-death and death-Birth updating - Svoboda, Jakub; Joshi, Soham Shrikant; Tkadlec, Josef; Chatterjee, Krishnendu (PLoS Computational Biology)
Populations evolve by accumulating advantageous mutations. Every population has some spatial structure that can be modeled by an underlying network. The network then influences the probability that new advantageous mutations fixate. Amplifiers of selection are networks that increase the fixation probability of advantageous mutants, as compared to the unstructured fully-connected network. Whether or not a network is an amplifier depends on the choice of the random process that governs the evolutionary dynamics. Two popular choices are Moran process with Birth-death updating and Moran process with death-Birth updating. Interestingly, while some networks are amplifiers under Birth-death updating and other networks are amplifiers under death-Birth updating, so far no spatial structures have been found that function as an amplifier under both types of updating simultaneously. In this work, we identify networks that act as amplifiers of selection under both versions of the Moran process. The amplifiers are robust, modular, and increase fixation probability for any mutant fitness advantage in a range r ∈ (1, 1.2). To complement this positive result, we also prove that for certain quantities closely related to fixation probability, it is impossible to improve them simultaneously for both versions of the Moran process. Together, our results highlight how the two versions of the Moran process differ and what they have in common.

Mechanical forces in plant tissue matrix orient cell divisions via microtubule stabilization - Hörmayer, Lukas; Montesinos López, Juan C; Trozzi, N; Spona, Leonhard; Yoshida, Saiko; Marhavá, Petra; Caballero Mancebo, Silvia; Benková, Eva; Heisenberg, Carl-Philipp J; Dagdas, Y; Majda, M; Friml, Jiří (Dev Cell)
Plant morphogenesis relies exclusively on oriented cell expansion and division. Nonetheless, the mechanism(s) determining division plane orientation remain elusive. Here, we studied tissue healing after laser-assisted wounding in roots of Arabidopsis thaliana and uncovered how mechanical forces stabilize and reorient the microtubule cytoskeleton for the orientation of cell division. We identified that root tissue functions as an interconnected cell matrix, with a radial gradient of tissue extendibility causing predictable tissue deformation after wounding. This deformation causes instant redirection of expansion in the surrounding cells and reorientation of microtubule arrays, ultimately predicting cell division orientation. Microtubules are destabilized under low tension, whereas stretching of cells, either through wounding or external aspiration, immediately induces their polymerization. The higher microtubule abundance in the stretched cell parts leads to the reorientation of microtubule arrays and, ultimately, informs cell division planes. This provides a long-sought mechanism for flexible re-arrangement of cell divisions by mechanical forces for tissue reconstruction and plant architecture.

Local adaptation, genetic load and extinction in metapopulations - Olusanya, Oluwafunmilola O
In nature, different species find their niche in a range of environments, each with its unique characteristics. While some thrive in uniform (homogeneous) landscapes where environmental conditions stay relatively consistent across space, others traverse the complexities of spatially heterogeneous terrains. Comprehending how species are distributed and how they interact within these landscapes holds the key to gaining insights into their evolutionary dynamics while also informing conservation and management strategies. For species inhabiting heterogeneous landscapes, when the rate of dispersal is low compared to spatial fluctuations in selection pressure, localized adaptations may emerge. Such adaptation in response to varying selection strengths plays an important role in the persistence of populations in our rapidly changing world. Hence, species in nature are continuously in a struggle to adapt to local environmental conditions, to ensure their continued survival. Natural populations can often adapt in time scales short enough for evolutionary changes to influence ecological dynamics and vice versa, thereby creating a feedback between evolution and demography. The analysis of this feedback and the relative contributions of gene flow, demography, drift, and natural selection to genetic variation and differentiation has remained a recurring theme in evolutionary biology. Nevertheless, the effective role of these forces in maintaining variation and shaping patterns of diversity is not fully understood. Even in homogeneous environments devoid of local adaptations, such understanding remains elusive. Understanding this feedback is crucial, for example in determining the conditions under which extinction risk can be mitigated in peripheral populations subject to deleterious mutation accumulation at the edges of species’ ranges as well as in highly fragmented populations. In this thesis we explore both uniform and spatially heterogeneous metapopulations, investigating and providing theoretical insights into the dynamics of local adaptation in the latter and examining the dynamics of load and extinction as well as the impact of joint ecological and evolutionary (eco-evolutionary) dynamics in the former. The thesis is divided into 5 chapters. Chapter 1 provides a general introduction into the subject matter, clarifying concepts and ideas used throughout the thesis. In chapter 2, we explore how fast a species distributed across a heterogeneous landscape adapts to changing conditions marked by alterations in carrying capacity, selection pressure, and migration rate. In chapter 3, we investigate how migration selection and drift influences adaptation and the maintenance of variation in a metapopulation with three habitats, an extension of previous models of adaptation in two habitats. We further develop analytical approximations for the critical threshold required for polymorphism to persist. The focus of chapter 4 of the thesis is on understanding the interplay between ecology and evolution as coupled processes. We investigate how eco-evolutionary feedback between migration, selection, drift, and demography influences eco-evolutionary outcomes in marginal populations subject to deleterious mutation accumulation. Using simulations as well as theoretical approximations of the coupled dynamics of population size and allele frequency, we analyze how gene flow from a large mainland source influences genetic load and population size on an island (i.e., in a marginal population) under genetically realistic assumptions. Analyses of this sort are important because small isolated populations, are repeatedly affected by complex interactions between ecological and evolutionary processes, which can lead to their death. Understanding these interactions can therefore provide an insight into the conditions under which extinction risk can be mitigated in peripheral populations thus, contributing to conservation and restoration efforts. Chapter 5 extends the analysis in chapter 4 to consider the dynamics of load (due to deleterious mutation accumulation) and extinction risk in a metapopulation. We explore the role of gene flow, selection, and dominance on load and extinction risk and further pinpoint critical thresholds required for metapopulation persistence. Overall this research contributes to our understanding of ecological and evolutionary mechanisms that shape species’ persistence in fragmented landscapes, a crucial foundation for successful conservation efforts and biodiversity management.

Multiple charge carrier species as a possible cause for triboelectric cycles - Sobarzo Ponce, Juan Carlos A; Waitukaitis, Scott R (Physical Review E)
The tendency of materials to order in triboelectric series has prompted suggestions that contact electrification might have a single, unified underlying description. However, the possibility of “triboelectric cycles,” i.e., series that loop back onto themselves, is seemingly at odds with such a coherent description. In this work, we propose that if multiple charge carrying species are at play, both triboelectric series and cycles are possible. We show how series arise naturally if only a single charge carrier species is involved and if the driving mechanism is approach toward thermodynamic equilibrium, and simultaneously, that cycles are forbidden under such conditions. Suspecting multiple carriers might relax the situation, we affirm this is the case by explicit construction of a cycle involving two carriers, and then extend this to show how more complex cycles emerge. Our work highlights the importance of series and cycles towards determining the underlying mechanism(s) and carrier(s) in contact electrification.

A note on the binding energy for Bosons in the mean-field limit - Bossmann, Lea; Leopold, Nikolai K; Mitrouskas, David Johannes; Petrat, Sören P (Journal of Statistical Physics)
We consider a gas of N weakly interacting bosons in the ground state. Such gases exhibit Bose–Einstein condensation. The binding energy is defined as the energy it takes to remove one particle from the gas. In this article, we prove an asymptotic expansion for the binding energy, and compute the first orders explicitly for the homogeneous gas. Our result addresses in particular a conjecture by Nam (Lett Math Phys 108(1):141–159, 2018), and provides an asymptotic expansion of the ionization energy of bosonic atoms.

Scaling limits of random walks, harmonic profiles, and stationary nonequilibrium states in Lipschitz domains - Dello Schiavo, Lorenzo; Portinale, Lorenzo; Sau, Federico (Annals of Applied Probability)
We consider the open symmetric exclusion (SEP) and inclusion (SIP) processes on a bounded Lipschitz domain Ω, with both fast and slow boundary. For the random walks on Ω dual to SEP/SIP we establish: a functional-CLT-type convergence to the Brownian motion on Ω with either Neumann (slow boundary), Dirichlet (fast boundary), or Robin (at criticality) boundary conditions; the discrete-to-continuum convergence of the corresponding harmonic profiles. As a consequence, we rigorously derive the hydrodynamic and hydrostatic limits for SEP/SIP on Ω, and analyze their stationary nonequilibrium fluctuations. All scaling limit results for SEP/SIP concern finite-dimensional distribution convergence only, as our duality techniques do not require to establish tightness for the fields associated to the particle systems.

Interplay of EXO70 and MLO proteins modulates trichome cell wall composition and susceptibility to powdery mildew - Huebbers, Jan W.; Caldarescu, George A.; Kubátová, Zdeňka; Sabol, Peter; Levecque, Sophie C.J.; Kuhn, Hannah; Kulich, Ivan; Reinstädler, Anja; Büttgen, Kim; Manga-Robles, Alba; Mélida, Hugo; Pauly, Markus; et al. (Plant Cell)
Exocyst component of 70-kDa (EXO70) proteins are constituents of the exocyst complex implicated in vesicle tethering during exocytosis. MILDEW RESISTANCE LOCUS O (MLO) proteins are plant-specific calcium channels and some MLO isoforms enable fungal powdery mildew pathogenesis. We here detected an unexpected phenotypic overlap of Arabidopsis thaliana exo70H4 and mlo2 mlo6 mlo12 triple mutant plants regarding the biogenesis of leaf trichome secondary cell walls. Biochemical and Fourier transform infrared spectroscopic analyses corroborated deficiencies in the composition of trichome cell walls in these mutants. Transgenic lines expressing fluorophore-tagged EXO70H4 and MLO exhibited extensive colocalization of these proteins. Furthermore, mCherry-EXO70H4 mislocalized in trichomes of the mlo triple mutant and, vice versa, MLO6-GFP mislocalized in trichomes of the exo70H4 mutant. Expression of GFP-marked PMR4 callose synthase, a known cargo of EXO70H4-dependent exocytosis, revealed reduced cell wall delivery of GFP-PMR4 in trichomes of mlo triple mutant plants. In vivo protein–protein interaction assays in plant and yeast cells uncovered isoform-preferential interactions between EXO70.2 subfamily members and MLO proteins. Finally, exo70H4 and mlo6 mutants, when combined, showed synergistically enhanced resistance to powdery mildew attack. Taken together, our data point to an isoform-specific interplay of EXO70 and MLO proteins in the modulation of trichome cell wall biogenesis and powdery mildew susceptibility.

Tuning the Josephson diode response with an ac current - Seoane Souto, Rubén; Leijnse, Martin; Schrade, Constantin; Valentini, Marco; Katsaros, Georgios; Danon, Jeroen (Physical Review Research)
Josephson diodes are superconducting elements that show an asymmetry in the critical current depending on the direction of the current. Here, we theoretically explore how an alternating current bias can tune the response of such a diode. We show that for slow driving there is always a regime where the system can only carry zero-voltage dc current in one direction, thus effectively behaving as an ideal Josephson diode. Under fast driving, the diode efficiency is also tunable, although the ideal regime cannot be reached in this case. We also investigate the residual dissipation due to the time-dependent current bias and show that it remains small. All our conclusions are solely based on the critical current asymmetry of the junction, and are thus compatible with any Josephson diode.

Learning dynamical models of single and collective cell migration: a review - Brückner, David; Broedersz, Chase P. (Reports on Progress in Physics)
Single and collective cell migration are fundamental processes critical for physiological phenomena ranging from embryonic development and immune response to wound healing and cancer metastasis. To understand cell migration from a physical perspective, a broad variety of models for the underlying physical mechanisms that govern cell motility have been developed. A key challenge in the development of such models is how to connect them to experimental observations, which often exhibit complex stochastic behaviours. In this review, we discuss recent advances in data-driven theoretical approaches that directly connect with experimental data to infer dynamical models of stochastic cell migration. Leveraging advances in nanofabrication, image analysis, and tracking technology, experimental studies now provide unprecedented large datasets on cellular dynamics. In parallel, theoretical efforts have been directed towards integrating such datasets into physical models from the single cell to the tissue scale with the aim of conceptualising the emergent behaviour of cells. We first review how this inference problem has been addressed in both freely migrating and confined cells. Next, we discuss why these dynamics typically take the form of underdamped stochastic equations of motion, and how such equations can be inferred from data. We then review applications of data-driven inference and machine learning approaches to heterogeneity in cell behaviour, subcellular degrees of freedom, and to the collective dynamics of multicellular systems. Across these applications, we emphasise how data-driven methods can be integrated with physical active matter models of migrating cells, and help reveal how underlying molecular mechanisms control cell behaviour. Together, these data-driven approaches are a promising avenue for building physical models of cell migration directly from experimental data, and for providing conceptual links between different length-scales of description.

Dynamics and scaling of internally cooled convection - Agasthya, Lokahith N; Muller, Caroline J (Communications in Nonlinear Science and Numerical Simulation)
Our goal is to investigate fundamental properties of the system of internally cooled convection. The system consists of an upward thermal flux at the lower boundary, a mean temperature lapse-rate and a constant cooling term in the bulk with the bulk cooling in thermal equilibrium with the input heat flux. This simple model represents idealised dry convection in the atmospheric boundary layer, where the cooling mimics the radiative cooling to space notably through longwave radiation. We perform linear stability analysis of the model for different values of the mean stratification to derive the critical forcing above which the fluid is convectively unstable to small perturbations. The dynamic behavior of the fluid system is described and the scaling of various important measured quantities such as the total vertical convective heat flux and the upward mass flux is measured. We introduce a lapse-rate dependent dimensionless Rayleigh-number Ray that determines the behavior of the system, finding that the convective heat-flux and mass-flux scale approximately as Ray0.5 and Ray0.7 respectively. The area-fraction of the domain that is occupied by upward and downward moving fluid and the skewness of the vertical velocity are studied to understand the asymmetry inherent in the system. We conclude with a short discussion on the relevance to atmospheric convection and the scope for further investigations of atmospheric convection using similar simplified approaches.

Polycrystalline phases engineered in-situ in polyaniline-graphene composite evoluting an exceptional stability and high charge storage capacity: An EIS investigative approach to evaluate material's stability - Mahato, Neelima; Singh, Saurabh; Sreekanth, T. V.M.; Yoo, Kisoo; Kim, Jonghoon (Journal of Energy Storage)
Development of electroactive materials exhibiting high performance with superior stability is crucial in the field of supercapacitors and battery research. We report on synthesis of highly stable composite of semi-polycrystalline polyaniline and graphene (SPani-graphene) and its application in supercapacitor electrodes. The electrochemical behavior and device performance of the electrodes were investigated through cyclic voltammetry (CV), galvanostatic charge-discharge GCD) and electrochemical impedance spectroscopy (EIS) in a 3-electrode and a 2-electrode (device) cell configurations, repectively. The cell specific capacitance (Cell Csp) achieved from the 2-electrode symmetric cell configuration was 525.5 F g−1 at 0.1 A g−1 using polymer gel electrolyte (PGE). The PGE in this work is xanthan gum jellied in 1 M aq. Na2SO4. The maximum energy density and power density achieved from the device was 46.7 Wh kg−1 and 16.16 kW kg−1, respectively, at 0.4 A g−1. Furthermore, the device exhibits an excellent retention of cell specific capacitance and coulombic efficiency of 97 % and 94 %, respectively, over 10,000 continuous GCD cycles, indicating an excellent rate capability as well as a promising power management. To investigate the material's electrochemical durability, a detailed EIS study has been carried out using both, 3-electrode, and 2-electrode cell configurations, before and after long cycling test (over 10,000 continuous GCD cycles). Our thorough experimentation delivers satisfactory results and has been explained in detail in the manuscript. Hereby, we propose that the EIS technique can be adopted for investigating materials' electrochemical stability, in addition to long CV and GCD cycles in the field of supercapacitors and battery research.

Scalable enumeration of trap spaces in boolean networks via answer set programming - Trinh, Giang; Benhamou, Belaid; Pastva, Samuel; Soliman, Sylvain (Proceedings of the 38th AAAI Conference on Artificial Intelligence)
Boolean Networks (BNs) are widely used as a modeling formalism in several domains, notably systems biology and computer science. A fundamental problem in BN analysis is the enumeration of trap spaces, which are hypercubes in the state space that cannot be escaped once entered. Several methods have been proposed for enumerating trap spaces, however they often suffer from scalability and efficiency issues, particularly for large and complex models. To our knowledge, the most efficient and recent methods for the trap space enumeration all rely on Answer Set Programming (ASP), which has been widely applied to the analysis of BNs. Motivated by these considerations, our work proposes a new method for enumerating trap spaces in BNs using ASP. We evaluate the method on a mix of 250+ real-world and 400+ randomly generated BNs, showing that it enables analysis of models beyond the capabilities of existing tools (namely pyboolnet, mpbn, trappist, and trapmvn).

Lifelong persistence of nuclear RNAs in the mouse brain - Zocher, Sara; Mccloskey, Asako; Karasinsky, Anne; Schulte, Roberta; Friedrich, Ulrike; Lesche, Mathias; Rund, Nicole; Gage, Fred H.; Hetzer, Martin W; Toda, Tomohisa (Science)
Genomic DNA that resides in the nuclei of mammalian neurons can be as old as the organism itself. The life span of nuclear RNAs, which are critical for proper chromatin architecture and transcription regulation, has not been determined in adult tissues. In this work, we identified and characterized nuclear RNAs that do not turn over for at least 2 years in a subset of postnatally born cells in the mouse brain. These long-lived RNAs were stably retained in nuclei in a neural cell type–specific manner and were required for the maintenance of heterochromatin. Thus, the life span of neural cells may depend on both the molecular longevity of DNA for the storage of genetic information and also the extreme stability of RNA for the functional organization of chromatin.

Hitchin map on even very stable upward flows - González, Miguel; Hausel, Tamás (International Journal of Mathematics)
We define even very stable Higgs bundles and study the Hitchin map restricted to their upward flows. In the GLn case, we classify the type (1,…,1) examples, and find that they are governed by a root system formed by the roots of even height. We discuss how the spectrum of equivariant cohomology of real and quaternionic Grassmannians, 4n-spheres and the real Cayley plane appear to describe the Hitchin map on even cominuscule upward flows. The even upward flows in question are the same as upward flows in Higgs bundle moduli spaces for quasi-split inner real forms. The latter spaces have been pioneered by Oscar García-Prada and his collaborators.

Density of rational points on some quadric bundle threefolds - Bonolis, Dante; Browning, Timothy D; Huang, Zhizhong (Mathematische Annalen)
We prove the Manin–Peyre conjecture for the number of rational points of bounded height outside of a thin subset on a family of Fano threefolds of bidegree (1, 2).

ALMA survey of a massive node of the Cosmic Web at z ∼ 3: I. Discovery of a large overdensity of CO emitters - Pensabene, A.; Cantalupo, S.; Cicone, C.; Decarli, R.; Galbiati, M.; Ginolfi, M.; De Beer, S.; Fossati, M.; Fumagalli, M.; Lazeyras, T.; Pezzulli, G.; Travascio, A.; et al. (Astronomy and Astrophysics)
Submillimeter surveys toward overdense regions in the early Universe are essential for uncovering the obscured star formation and the cold gas content of assembling galaxies within massive dark matter halos. In this work, we present deep ALMA mosaic observations covering an area of ∼2′×2′ around MUSE Quasar Nebula 01 (MQN01), one of the largest and brightest Ly-α emitting nebulae discovered thus far; it surrounds a radio-quiet quasar at z ≃ 3.25. Our observations target the 1.2 and the 3 mm dust continuum as well as the carbon monoxide CO(4–3) transition in galaxies in the vicinity of the quasar. We identify a robust sample of 11 CO-line-emitting galaxies (including a closely separated quasar companion) that lie within ±4000 km s−1 of the quasar systemic redshift. A fraction of these objects were missed in previous deep rest-frame optical/UV surveys, which highlights the critical role of (sub)millimeter imaging. We also detect a total of 11 sources revealed in the dust continuum at 1.2 mm; six of them have either high-fidelity spectroscopic redshift information from rest-frame UV metal absorptions or the CO(4–3) line that places them in the same narrow redshift range. A comparison of the CO luminosity function and 1.2 mm number count density with those of the general fields points to a galaxy overdensity of δ > 10. We find evidence of a systematic flattening at the bright end of the CO luminosity function with respect to the trend measured in blank fields. Our findings reveal that galaxies in dense regions at z ∼ 3 are more massive and significantly richer in molecular gas than galaxies in fields, which enables a faster and accelerated assembly. This is the first in a series of studies aimed at characterizing one of the densest regions of the Universe found so far at z > 3.

Postsynaptic receptors regulate presynaptic transmitter stability through transsynaptic bridges - Godavarthi, Swetha K.; Hiramoto, Masaki; Ignatyev, Yuri; Levin, Jacqueline B.; Li, Hui Quan; Pratelli, Marta; Borchardt, Jennifer; Czajkowski, Cynthia; Borodinsky, Laura N.; Sweeney, Lora Beatrice Jaeger; Cline, Hollis T.; Spitzer, Nicholas C. (PNAS)
Stable matching of neurotransmitters with their receptors is fundamental to synapse function and reliable communication in neural circuits. Presynaptic neurotransmitters regulate the stabilization of postsynaptic transmitter receptors. Whether postsynaptic receptors regulate stabilization of presynaptic transmitters has received less attention. Here, we show that blockade of endogenous postsynaptic acetylcholine receptors (AChR) at the neuromuscular junction destabilizes the cholinergic phenotype in motor neurons and stabilizes an earlier, developmentally transient glutamatergic phenotype. Further, expression of exogenous postsynaptic gamma-aminobutyric acid type A receptors (GABAA receptors) in muscle cells stabilizes an earlier, developmentally transient GABAergic motor neuron phenotype. Both AChR and GABAA receptors are linked to presynaptic neurons through transsynaptic bridges. Knockdown of specific components of these transsynaptic bridges prevents stabilization of the cholinergic or GABAergic phenotypes. Bidirectional communication can enforce a match between transmitter and receptor and ensure the fidelity of synaptic transmission. Our findings suggest a potential role of dysfunctional transmitter receptors in neurological disorders that involve the loss of the presynaptic transmitter.

Sharp interface limit for a Navier–Stokes/Allen–Cahn system in the case of a vanishing mobility - Abels, Helmut; Fei, Mingwen; Moser, Maximilian (Calculus of Variations and Partial Differential Equations)
We consider the sharp interface limit of a Navier-Stokes/Allen Cahn equation in a bounded smooth domain in two space dimensions, in the case of vanishing mobility mε=ε√, where the small parameter ε>0 related to the thickness of the diffuse interface is sent to zero. For well-prepared initial data and sufficiently small times, we rigorously prove convergence to the classical two-phase Navier-Stokes system with surface tension. The idea of the proof is to use asymptotic expansions to construct an approximate solution and to estimate the difference of the exact and approximate solutions with a spectral estimate for the (at the approximate solution) linearized Allen-Cahn operator. In the calculations we use a fractional order ansatz and new ansatz terms in higher orders leading to a suitable ε-scaled and coupled model problem. Moreover, we apply the novel idea of introducing ε-dependent coordinates.

Generalised quadratic forms over totally real number fields - Browning, Timothy D; Pierce, Lillian B.; Schindler, Damaris (Journal of the Institute of Mathematics of Jussieu)
We introduce a new class of generalised quadratic forms over totally real number fields, which is rich enough to capture the arithmetic of arbitrary systems of quadrics over the rational numbers. We explore this connection through a version of the Hardy–Littlewood circle method over number fields.

Generalized minimum 0-extension problem and discrete convexity - Dvorak, Martin; Kolmogorov, Vladimir (Mathematical Programming)
Given a fixed finite metric space (V,μ), the {\em minimum 0-extension problem}, denoted as 0-Ext[μ], is equivalent to the following optimization problem: minimize function of the form minx∈Vn∑ifi(xi)+∑ijcijμ(xi,xj) where cij,cvi are given nonnegative costs and fi:V→R are functions given by fi(xi)=∑v∈Vcviμ(xi,v). The computational complexity of 0-Ext[μ] has been recently established by Karzanov and by Hirai: if metric μ is {\em orientable modular} then 0-Ext[μ] can be solved in polynomial time, otherwise 0-Ext[μ] is NP-hard. To prove the tractability part, Hirai developed a theory of discrete convex functions on orientable modular graphs generalizing several known classes of functions in discrete convex analysis, such as L♮-convex functions. We consider a more general version of the problem in which unary functions fi(xi) can additionally have terms of the form cuv;iμ(xi,{u,v}) for {u,v}∈F, where set F⊆(V2) is fixed. We extend the complexity classification above by providing an explicit condition on (μ,F) for the problem to be tractable. In order to prove the tractability part, we generalize Hirai's theory and define a larger class of discrete convex functions. It covers, in particular, another well-known class of functions, namely submodular functions on an integer lattice. Finally, we improve the complexity of Hirai's algorithm for solving 0-Ext on orientable modular graphs.
Keywords: minimum 0-extension problem; metric labeling problem; discrete metric spaces; metric extensions; computational complexity; valued constraint satisfaction problems; discrete convex analysis; L-convex functions

Pushing thermal conductivity to its lower limit in crystals with simple structures - Zeng, Zezhu; Shen, Xingchen; Cheng, Ruihuan; Perez, Olivier; Ouyang, Niuchang; Fan, Zheyong; Lemoine, Pierric; Raveau, Bernard; Guilmeau, Emmanuel; Chen, Yue (Nature Communications)
Materials with low thermal conductivity usually have complex crystal structures. Herein we experimentally find that a simple crystal structure material AgTlI2 (I4/mcm) owns an extremely low thermal conductivity of 0.25 W/mK at room temperature. To understand this anomaly, we perform in-depth theoretical studies based on ab initio molecular dynamics simulations and anharmonic lattice dynamics. We find that the unique atomic arrangement and weak chemical bonding provide a permissive environment for strong oscillations of Ag atoms, leading to a considerable rattling behaviour and giant lattice anharmonicity. This feature is also verified by the experimental probability density function refinement of single-crystal diffraction. The particularly strong anharmonicity breaks down the conventional phonon gas model, giving rise to non-negligible wavelike phonon behaviours in AgTlI2 at 300 K. Intriguingly, unlike many strongly anharmonic materials where a small propagative thermal conductivity is often accompanied by a large diffusive thermal conductivity, we find an unusual coexistence of ultralow propagative and diffusive thermal conductivities in AgTlI2 based on the thermal transport unified theory. This study underscores the potential of simple crystal structures in achieving low thermal conductivity and encourages further experimental research to enrich the family of materials with ultralow thermal conductivity.

Square-free values of random polynomials - Browning, Timothy D; Shparlinski, Igor E. (Journal of Number Theory)
The question of whether or not a given integral polynomial takes infinitely many square-free values has only been addressed unconditionally for polynomials of degree at most 3. We address this question, on average, for polynomials of arbitrary degree.

Bubaak-SpLit: Split what you cannot verify (Competition contribution) - Chalupa, Marek; Richter, Cedric (30th International Conference on Tools and Algorithms for the Construction and Analysis of Systems)
BUBAAK-SpLit is a tool for dynamically splitting verification tasks into parts that can then be analyzed in parallel. It is built on top of BUBAAK, a tool designed for running combinations of verifiers in parallel. In contrast to BUBAAK, that directly invokes verifiers on the inputs, BUBAAK-SpLit first starts by splitting the input program into multiple modified versions called program splits. During the splitting process, BUBAAK-SpLit utilizes a weak verifier (in our case symbolic execution with a short timelimit) to analyze each generated program split. If the weak verifier fails on a program split, we split this program split again and start the verification process again on the generated program splits. We run the splitting process until a predefined number of hard-to-verify program splits is generated or a splitting limit is reached. During the main verification phase, we run a combination of BUBAAK-LEE and SLOWBEAST in parallel on the remaining unsolved parts of the verification task.

Role of dynamin-related proteins 2 and SH3P2 in clathrin-mediated endocytosis in Arabidopsis thaliana - Gnyliukh, Nataliia; Johnson, Alexander J; Nagel, MK; Monzer, Aline; Babic, David; Hlavata, Annamaria; Alotaibi, SS; Isono, E; Loose, Martin; Friml, Jiří (Journal of Cell Science)
Clathrin-mediated endocytosis (CME) is vital for the regulation of plant growth and development by controlling plasma membrane protein composition and cargo uptake. CME relies on the precise recruitment of regulators for vesicle maturation and release. Homologues of components of mammalian vesicle scission are strong candidates to be part of the scission machinery in plants, but the precise roles of these proteins in this process are not fully understood. Here, we characterised the roles of Plant Dynamin-Related Proteins 2 (DRP2s) and SH3-domain containing protein 2 (SH3P2), the plant homologue to Dynamins’ recruiters, like Endophilin and Amphiphysin, in the CME by combining high-resolution imaging of endocytic events in vivo and characterisation of the purified proteins in vitro. Although DRP2s and SH3P2 arrive similarly late during CME and physically interact, genetic analysis of the sh3p123 triple-mutant and complementation assays with non-SH3P2-interacting DRP2 variants suggests that SH3P2 does not directly recruit DRP2s to the site of endocytosis. These observations imply that despite the presence of many well-conserved endocytic components, plants have acquired a distinct mechanism for CME.

In-situ engineered highly crystalline polythiophene empowered electrochemical capacitor-I: Synthesis, characterization, and electrochemical charge storage - Mahato, Neelima; Singh, Saurabh; Sreekanth, T. V.M.; Yoo, Kisoo; Kim, Jonghoon (Materials Letters)
We report on synthesis of highly crystalline polythiophene and its application in supercapacitor electrodes. The material exhibits a remarkably stable electrochemical behavior and an excellent device performance. The device delivers an electrode specific capacitance (Csp) of 129.13F g−1, Cell Csp of 32.28F g−1 at 0.5 A/g; energy, and power densities of ∼ 3 Wh kg−1 and 250 W kg -1, respectively at 0.5 A/g. Also, it exhibits an excellent retention of Cell Csp and coulombic efficiency up to ∼ 95 % over 10,000 continuous galvanostatic charge discharge (GCD) cycles indicating a remarkable performance by a standalone, pristine and undoped polythiophene. Electrochemical impedance spectroscopy (EIS) studies further suggest material’s stable capacitive behavior. The material’s enhanced electrochemical properties, stable behavior and outstanding performance in device application are attributed to the crystalline phases present in the polymer matrix achievable via a slow rate of synthesis; overall, an edge over other conventional synthesis methods.

Quantum Talagrand, KKL and Friedgut’s theorems and the learnability of quantum boolean functions - Rouzé, Cambyse; Wirth, Melchior; Zhang, Haonan (Communications in Mathematical Physics)
We extend three related results from the analysis of influences of Boolean functions to the quantum setting, namely the KKL theorem, Friedgut’s Junta theorem and Talagrand’s variance inequality for geometric influences. Our results are derived by a joint use of recently studied hypercontractivity and gradient estimates. These generic tools also allow us to derive generalizations of these results in a general von Neumann algebraic setting beyond the case of the quantum hypercube, including examples in infinite dimensions relevant to quantum information theory such as continuous variables quantum systems. Finally, we comment on the implications of our results as regards to noncommutative extensions of isoperimetric type inequalities, quantum circuit complexity lower bounds and the learnability of quantum observables.

Protein-Protein Interactions Visualized by Bimolecular Fluorescence Complementation in Arabidopsis thaliana Protoplasts from Leaf - Jayasree, Aswathy; Salava, Hymavathi; Nodzynski, Tomasz; Sravankumar, Thula (Plant Functional Genomics)
Bimolecular fluorescence complementation (BiFC) is a powerful tool for studying protein-protein interactions in living cells. By fusing interacting proteins to fluorescent protein fragments, BiFC allows visualization of spatial localization patterns of protein complexes. This method has been adapted to a variety of expression systems in different organisms and is widely used to study protein interactions in plant cells. The Agrobacterium-mediated transient expression protocol for BiFC assays in Nicotiana benthamiana (N. benthamiana) leaf cells is widely used, but in this chapter, a method for BiFC assay using Arabidopsis thaliana protoplasts is presented.

Discovery of recessive effect of human polymerase δ proofreading deficiency through mutational analysis of POLD1-mutated normal and cancer cells - Andrianova, Maria A.; Seplyarskiy, Vladimir B.; Terradas, Mariona; Sánchez-Heras, Ana Beatriz; Mur, Pilar; Soto, José Luis; Aiza, Gemma; Borràs, Emma; Kondrashov, Fyodor; Kondrashov, Alexey S.; Bazykin, Georgii A.; Valle, Laura (European Journal of Human Genetics)
Constitutional heterozygous pathogenic variants in the exonuclease domain of POLE and POLD1, which affect the proofreading activity of the corresponding polymerases, cause a cancer predisposition syndrome characterized by increased risk of gastrointestinal polyposis, colorectal cancer, endometrial cancer and other tumor types. The generally accepted explanation for the connection between the disruption of the proofreading activity of polymerases epsilon and delta and cancer development is through an increase in the somatic mutation rate. Here we studied an extended family with multiple members heterozygous for the pathogenic POLD1 variant c.1421T>C p.(Leu474Pro), which segregates with the polyposis and cancer phenotypes. Through the analysis of mutational patterns of patient-derived fibroblasts colonies and de novo mutations obtained by parent-offspring comparisons, we concluded that heterozygous POLD1 L474P just subtly increases the somatic and germline mutation burden. In contrast, tumors developed in individuals with a heterozygous mutation in the exonuclease domain of POLD1, including L474P, have an extremely high mutation rate (>100 mut/Mb) associated with signature SBS10d. We solved this contradiction through the observation that tumorigenesis involves somatic inactivation of the wildtype POLD1 allele. These results imply that exonuclease deficiency of polymerase delta has a recessive effect on mutation rate.

Proximity-induced gapless superconductivity in two-dimensional Rashba semiconductor in magnetic field - Babkin, Serafim; Higginbotham, Andrew P; Serbyn, Maksym (SciPost Physics)
Two-dimensional semiconductor-superconductor heterostructures form the foundation of numerous nanoscale physical systems. However, measuring the properties of such heterostructures, and characterizing the semiconductor in-situ is challenging. A recent experimental study by [Phys. Rev. Lett. 128, 107701 (2022)] was able to probe the semiconductor within the heterostructure using microwave measurements of the superfluid density. This work revealed a rapid depletion of superfluid density in semiconductor, caused by the in-plane magnetic field which in presence of spin-orbit coupling creates so-called Bogoliubov Fermi surfaces. The experimental work used a simplified theoretical model that neglected the presence of non-magnetic disorder in the semiconductor, hence describing the data only qualitatively. Motivated by experiments, we introduce a theoretical model describing a disordered semiconductor with strong spin-orbit coupling that is proximitized by a superconductor. Our model provides specific predictions for the density of states and superfluid density. Presence of disorder leads to the emergence of a gapless superconducting phase, that may be viewed as a manifestation of Bogoliubov Fermi surface. When applied to real experimental data, our model showcases excellent quantitative agreement, enabling the extraction of material parameters such as mean free path and mobility, and estimating g-tensor after taking into account the orbital contribution of magnetic field. Our model can be used to probe in-situ parameters of other superconductor-semiconductor heterostructures and can be further extended to give access to transport properties.

Molecular dynamics simulations of heat transport using machine-learned potentials: A mini-review and tutorial on GPUMD with neuroevolution potentials - Dong, Haikuan; Shi, Yongbo; Ying, Penghua; Xu, Ke; Liang, Ting; Wang, Yanzhou; Zeng, Zezhu; Wu, Xin; Zhou, Wenjiang; Xiong, Shiyun; Chen, Shunda; Fan, Zheyong (Journal of Applied Physics)
Molecular dynamics (MD) simulations play an important role in understanding and engineering heat transport properties of complex materials. An essential requirement for reliably predicting heat transport properties is the use of accurate and efficient interatomic potentials. Recently, machine-learned potentials (MLPs) have shown great promise in providing the required accuracy for a broad range of materials. In this mini-review and tutorial, we delve into the fundamentals of heat transport, explore pertinent MD simulation methods, and survey the applications of MLPs in MD simulations of heat transport. Furthermore, we provide a step-by-step tutorial on developing MLPs for highly efficient and predictive heat transport simulations, utilizing the neuroevolution potentials as implemented in the GPUMD package. Our aim with this mini-review and tutorial is to empower researchers with valuable insights into cutting-edge methodologies that can significantly enhance the accuracy and efficiency of MD simulations for heat transport studies.

Identifying Pd9OX as the optimum catalyst for the direct synthesis of H2O2 through microkinetic modeling with coverage effects - Zhao, Jinyan; Yao, Zihao; Bunting, Rhys; Wang, Yaqiu; Wang, Jianguo (Chemical Engineering Science)
Identifying efficient active sites for the direct synthesis of hydrogen peroxide over Pd-based catalysts has been a subject of considerable debate. In this study, we employ particle swarm optimization method and density functional theory to explore the H2O2 synthesis mechanism on Pd, PdO, and the partially oxidized surface (Pd9OX). A comprehensive mechanism for Pd9OX is elucidated, and subsequent coverage-dependent kinetic analysis allows for a quantitative assessment of catalytic performance at the interphase. Our findings conclusively establish that the interphase between Pd and PdO represents the optimal active site. Phase diagram analysis further aids in determining stable structures under reaction conditions. At 298.15 K and under oxygen balance, the Pd9O6 surface remains stable throughout the reaction, demonstrating high activity and selectivity. This work underscores the significance of the interphase in comprehending catalytic performance and unveils promising avenues for optimizing catalyst performance by controlling reaction conditions and surface composition.

Limits to selection on standing variation in an asexual population - Barton, Nicholas H; Sachdeva, Himani (Theoretical Population Biology)
We consider how a population of N haploid individuals responds to directional selection on standing variation, with no new variation from recombination or mutation. Individuals have trait values z1,…,zN, which are drawn from a distribution ψ; the fitness of individual i is proportional to [Formula: see text] . For illustration, we consider the Laplace and Gaussian distributions, which are parametrised only by the variance V0, and show that for large N, there is a scaling limit which depends on a single parameter NV0. When selection is weak relative to drift (NV0≪1), the variance decreases exponentially at rate 1/N, and the expected ultimate gain in log fitness (scaled by V0), is just NV0, which is the same as Robertson's (1960) prediction for a sexual population. In contrast, when selection is strong relative to drift (NV0≫1), the ultimate gain can be found by approximating the establishment of alleles by a branching process in which each allele competes independently with the population mean and the fittest allele to establish is certain to fix. Then, if the probability of survival to time t∼1/V0 of an allele with value z is P(z), with mean P¯, the winning allele is the fittest of NP¯ survivors drawn from a distribution ψP/P¯. The expected ultimate change is ∼2log(1.15NV0) for a Gaussian distribution, and ∼-12log0.36NV0-log-log0.36NV0 for a Laplace distribution. This approach also predicts the variability of the process, and its dynamics; we show that in the strong selection regime, the expected genetic variance decreases as ∼t-3 at large times. We discuss how these results may be related to selection on standing variation that is spread along a linear chromosome.

SH3Ps recruit auxilin-like vesicle uncoating factors for clathrin-mediated endocytosis - Adamowski, Maciek; Randuch, Marek; Matijevic, Ivana; Narasimhan, Madhumitha; Friml, Jiří (Cell Reports)
Clathrin-mediated endocytosis (CME) is an essential process of cargo uptake operating in all eukaryotes. In animals and yeast, BAR-SH3 domain proteins, endophilins and amphiphysins, function at the conclusion of CME to recruit factors for vesicle scission and uncoating. Arabidopsis thaliana contains the BAR-SH3 domain proteins SH3P1–SH3P3, but their role is poorly understood. Here, we identify SH3Ps as functional homologs of endophilin/amphiphysin. SH3P1–SH3P3 bind to discrete foci at the plasma membrane (PM), and SH3P2 recruits late to a subset of clathrin-coated pits. The SH3P2 PM recruitment pattern is nearly identical to its interactor, a putative uncoating factor, AUXILIN-LIKE1. Notably, SH3P1–SH3P3 are required for most of AUXILIN-LIKE1 recruitment to the PM. This indicates a plant-specific modification of CME, where BAR-SH3 proteins recruit auxilin-like uncoating factors rather than the uncoating phosphatases, synaptojanins. SH3P1–SH3P3 act redundantly in overall CME with the plant-specific endocytic adaptor TPLATE complex but not due to an SH3 domain in its TASH3 subunit.

Enhancing thermoelectric performance of solutionpProcessed polycrystalline SnSe with PbSe nanocrystals - Liu, Yu; Lee, Seungho; Fiedler, Christine; Spadaro, Maria Chiara; Chang, Cheng; Li, Mingquan; Hong, Min; Arbiol, Jordi; Ibáñez, Maria (Chemical Engineering Journal)
There is a growing interest in cost-effective polycrystalline SnSe-based thermoelectric (TE) materials, which are able to replace the high performance but mechanically fragile and costly single-crystalline SnSe. In this study, we present a low-temperature solution-based approach to produce SnSe-PbSe nanocomposites with outstanding TE performance. Our method involves combining surfactant-free SnSe particles with oleate-capped PbSe nanocrystals in specific ratios, followed by thermal annealing and consolidation using spark plasma sintering. These nanocomposites are characterized by distinct compositional and structural properties that significantly impact their transport properties. In particular, the addition of oleate-capped PbSe nanocrystals results in: i) a reduction in the electrostatically adsorbed Na at the surface of the SnSe particles; ii) a reduction of Sn vacancies due to alloying with Pb; iii) an increase in grain boundary density; and iv) the formation of PbSnSe secondary phases. Notably, the SnSe-2.5 %PbSe nanocomposites demonstrate a 30 % decrease in thermal conductivity compared to that of the SnSe matrix. This reduction contributes to a maximum figure of merit (zT) of 1.75 at 788 K with a high average zT value of ca. 1.2 in the medium temperature range of 573–773 K. These values represent one of the highest reported in polycrystalline SnSe materials, showcasing the potential of our fabricated SnSe-PbSe nanocomposites for cost-effective TE applications.

Unraveling the mechanisms of PAMless DNA interrogation by SpRY-Cas9 - Hibshman, Grace N.; Bravo, Jack Peter Kelly; Hooper, Matthew M.; Dangerfield, Tyler L.; Zhang, Hongshan; Finkelstein, Ilya J.; Johnson, Kenneth A.; Taylor, David W. (Nature Communications)
CRISPR-Cas9 is a powerful tool for genome editing, but the strict requirement for an NGG protospacer-adjacent motif (PAM) sequence immediately next to the DNA target limits the number of editable genes. Recently developed Cas9 variants have been engineered with relaxed PAM requirements, including SpG-Cas9 (SpG) and the nearly PAM-less SpRY-Cas9 (SpRY). However, the molecular mechanisms of how SpRY recognizes all potential PAM sequences remains unclear. Here, we combine structural and biochemical approaches to determine how SpRY interrogates DNA and recognizes target sites. Divergent PAM sequences can be accommodated through conformational flexibility within the PAM-interacting region, which facilitates tight binding to off-target DNA sequences. Nuclease activation occurs ~1000-fold slower than for Streptococcus pyogenes Cas9, enabling us to directly visualize multiple on-pathway intermediate states. Experiments with SpG position it as an intermediate enzyme between Cas9 and SpRY. Our findings shed light on the molecular mechanisms of PAMless genome editing.

Hippocampal cholecystokinin-expressing interneurons regulate temporal coding and contextual learning - Rangel Guerrero, Dámaris K; Balueva, Kira; Barayeu, Uladzislau; Baracskay, Peter; Gridchyn, Igor; Nardin, Michele; Roth, Chiara N; Wulff, Peer; Csicsvari, Jozsef L (Neuron)
Cholecystokinin-expressing interneurons (CCKIs) are hypothesized to shape pyramidal cell-firing patterns and regulate network oscillations and related network state transitions. To directly probe their role in the CA1 region, we silenced their activity using optogenetic and chemogenetic tools in mice. Opto-tagged CCKIs revealed a heterogeneous population, and their optogenetic silencing triggered wide disinhibitory network changes affecting both pyramidal cells and other interneurons. CCKI silencing enhanced pyramidal cell burst firing and altered the temporal coding of place cells: theta phase precession was disrupted, whereas sequence reactivation was enhanced. Chemogenetic CCKI silencing did not alter the acquisition of spatial reference memories on the Morris water maze but enhanced the recall of contextual fear memories and enabled selective recall when similar environments were tested. This work suggests the key involvement of CCKIs in the control of place-cell temporal coding and the formation of contextual memories.

Linker histone H1 drives heterochromatin condensation via phase separation in Arabidopsis - He, Shengbo; Yu, Yiming; Wang, Liang; Zhang, Jingyi; Bai, Zhengyong; Li, Guohong; Li, Pilong; Feng, Xiaoqi (The Plant Cell)
In the eukaryotic nucleus, heterochromatin forms highly condensed, visible foci known as heterochromatin foci (HF). These HF are enriched with linker histone H1, a key player in heterochromatin condensation and silencing. However, it is unknown how H1 aggregates HF and condenses heterochromatin. In this study, we established that H1 facilitates heterochromatin condensation by enhancing inter- and intrachromosomal interactions between and within heterochromatic regions of the Arabidopsis (Arabidopsis thaliana) genome. We demonstrated that H1 drives HF formation via phase separation, which requires its C-terminal intrinsically disordered region (C-IDR). A truncated H1 lacking the C-IDR fails to form foci or recover HF in the h1 mutant background, whereas C-IDR with a short stretch of the globular domain (18 out of 71 amino acids) is sufficient to rescue both defects. In addition, C-IDR is essential for H1's roles in regulating nucleosome repeat length and DNA methylation in Arabidopsis, indicating that phase separation capability is required for chromatin functions of H1. Our data suggest that bacterial H1-like proteins, which have been shown to condense DNA, are intrinsically disordered and capable of mediating phase separation. Therefore, we propose that phase separation mediated by H1 or H1-like proteins may represent an ancient mechanism for condensing chromatin and DNA.

Wegner estimate and upper bound on the eigenvalue condition number of non-Hermitian random matrices - Erdös, László; Ji, Hong Chang (Communications on Pure and Applied Mathematics)
We consider N×N non-Hermitian random matrices of the form X+A, where A is a general deterministic matrix and N−−√X consists of independent entries with zero mean, unit variance, and bounded densities. For this ensemble, we prove (i) a Wegner estimate, i.e. that the local density of eigenvalues is bounded by N1+o(1) and (ii) that the expected condition number of any bulk eigenvalue is bounded by N1+o(1); both results are optimal up to the factor No(1). The latter result complements the very recent matching lower bound obtained in [15] (arXiv:2301.03549) and improves the N-dependence of the upper bounds in [5,6,32] (arXiv:1906.11819, arXiv:2005.08930, arXiv:2005.08908). Our main ingredient, a near-optimal lower tail estimate for the small singular values of X+A−z, is of independent interest.

Tuning synaptic strength by regulation of AMPA glutamate receptor localization - Stockwell, Imogen; Watson, Jake; Greger, Ingo H. (BioEssays)
Long-term potentiation (LTP) of excitatory synapses is a leading model to explain the concept of information storage in the brain. Multiple mechanisms contribute to LTP, but central amongst them is an increased sensitivity of the postsynaptic membrane to neurotransmitter release. This sensitivity is predominantly determined by the abundance and localization of AMPA-type glutamate receptors (AMPARs). A combination of AMPAR structural data, super-resolution imaging of excitatory synapses, and an abundance of electrophysiological studies are providing an ever-clearer picture of how AMPARs are recruited and organized at synaptic junctions. Here, we review the latest insights into this process, and discuss how both cytoplasmic and extracellular receptor elements cooperate to tune the AMPAR response at the hippocampal CA1 synapse.

Christensen–Evans theorem and extensions of GNS-symmetric quantum Markov semigroups - Wirth, Melchior (Journal of Functional Analysis)
In this article we prove a refined version of the Christensen–Evans theorem for generators of uniformly continuous GNS-symmetric quantum Markov semigroups. We use this result to show the existence of GNS-symmetric extensions of GNS-symmetric quantum Markov semigroups. In particular, this implies that the generators of GNS-symmetric quantum Markov semigroups on finite-dimensional von Neumann algebra can be written in the form specified by Alicki's theorem.

Depth in arrangements: Dehn–Sommerville–Euler relations with applications - Biswas, Ranita; Cultrera Di Montesano, Sebastiano; Edelsbrunner, Herbert; Saghafian, Morteza (Journal of Applied and Computational Topology)
The depth of a cell in an arrangement of n (non-vertical) great-spheres in Sd is the number of great-spheres that pass above the cell. We prove Euler-type relations, which imply extensions of the classic Dehn–Sommerville relations for convex polytopes to sublevel sets of the depth function, and we use the relations to extend the expressions for the number of faces of neighborly polytopes to the number of cells of levels in neighborly arrangements.

Investigating acute microglia response to seizure activity in vivo: Combining 2-Photon imaging and EEG recording - Murmann, Julie Stefanie

Developmental transformation of nanodomain coupling between Ca2+ channels and release sensors at a central GABAergic synapse - Chen, JingJing
The coupling between presynaptic Ca2+ channels and release sensors is a key factor that determines speed and efficacy of synapse transmission. At some excitatory synapses, channel–sensor coupling becomes tighter during development, and tightening is often associated with a switch in the reliance on different Ca2+ channel subtypes. However, the coupling topography at many synapses remains unknown, and it is unclear how it changes during development. To address this question, we analyzed the coupling configuration at the cerebellar basket cell (BC) to Purkinje cell (PC) synapse at different developmental stages, combining biophysical analysis, structural analysis, and modeling. Quantal analysis of BC–PC indicated that release probability decreased, while the number of functional sites increased during development. Although transmitter release persistently relied on P/Q-type Ca2+ channels in the time period postnatal day 7–23, effects of the Ca2+ chelator EGTA and BAPTA applied by intracellular pipette perfusion decreased during development, indicative of tightening of source-sensor coupling. Furthermore, presynaptic action potentials became shorter during development, suggesting reduced efficacy of Ca2+ channel activation. Structural analysis by freeze-fracture replica labeling (FRL) and transmission electron microscopy (EM) indicated that presynaptic P/Q-type Ca2+ channels formed nanoclusters throughout development, whereas docked vesicles were only clustered at later developmental stages. The number of functional release sites correlated better with the AZ number early in development, but match better with the Ca2+ channel cluster number at later stages. Modeling suggested a developmental transformation from a more random to a more clustered coupling nanotopography. Thus, presynaptic signaling developmentally approaches a point-to-point configuration, optimizing speed, reliability, and energy efficiency of synaptic transmission.

Developmental transformation of Ca2+ channel-vesicle nanotopography at a central GABAergic synapse - Chen, JingJing; Kaufmann, Walter; Chen, Chong; Arai, Itaru; Kim, Olena; Shigemoto, Ryuichi; Jonas, Peter M (Neuron)
The coupling between Ca2+ channels and release sensors is a key factor defining the signaling properties of a synapse. However, the coupling nanotopography at many synapses remains unknown, and it is unclear how it changes during development. To address these questions, we examined coupling at the cerebellar inhibitory basket cell (BC)-Purkinje cell (PC) synapse. Biophysical analysis of transmission by paired recording and intracellular pipette perfusion revealed that the effects of exogenous Ca2+ chelators decreased during development, despite constant reliance of release on P/Q-type Ca2+ channels. Structural analysis by freeze-fracture replica labeling (FRL) and transmission electron microscopy (EM) indicated that presynaptic P/Q-type Ca2+ channels formed nanoclusters throughout development, whereas docked vesicles were only clustered at later developmental stages. Modeling suggested a developmental transformation from a more random to a more clustered coupling nanotopography. Thus, presynaptic signaling developmentally approaches a point-to-point configuration, optimizing speed, reliability, and energy efficiency of synaptic transmission.

A Guide Toward Multi-scale and Quantitative Branching Analysis in the Mammary Gland - Hannezo, Edouard B; Scheele, Colinda L.G.J. (Cell Migration in Three Dimensions)
The mammary gland consists of a bilayered epithelial structure with an extensively branched morphology. The majority of this epithelial tree is laid down during puberty, during which actively proliferating terminal end buds repeatedly elongate and bifurcate to form the basic structure of the ductal tree. Mammary ducts consist of a basal and luminal cell layer with a multitude of identified sub-lineages within both layers. The understanding of how these different cell lineages are cooperatively driving branching morphogenesis is a problem of crossing multiple scales, as this requires information on the macroscopic branched structure of the gland, as well as data on single-cell dynamics driving the morphogenic program. Here we describe a method to combine genetic lineage tracing with whole-gland branching analysis. Quantitative data on the global organ structure can be used to derive a model for mammary gland branching morphogenesis and provide a backbone on which the dynamics of individual cell lineages can be simulated and compared to lineage-tracing approaches. Eventually, these quantitative models and experiments allow to understand the couplings between the macroscopic shape of the mammary gland and the underlying single-cell dynamics driving branching morphogenesis.

Dissipative dynamics of an impurity with spin-orbit coupling - Ghazaryan, Areg; Cappellaro, Alberto; Lemeshko, Mikhail; Volosniev, Artem (Physical Review Research)
Brownian motion of a mobile impurity in a bath is affected by spin-orbit coupling (SOC). Here, we discuss a Caldeira-Leggett-type model that can be used to propose and interpret quantum simulators of this problem in cold Bose gases. First, we derive a master equation that describes the model and explore it in a one-dimensional (1D) setting. To validate the standard assumptions needed for our derivation, we analyze available experimental data without SOC; as a byproduct, this analysis suggests that the quench dynamics of the impurity is beyond the 1D Bose-polaron approach at temperatures currently accessible in a cold-atom laboratory—motion of the impurity is mainly driven by dissipation. For systems with SOC, we demonstrate that 1D spin-orbit coupling can be gauged out even in the presence of dissipation—the information about SOC is incorporated in the initial conditions. Observables sensitive to this information (such as spin densities) can be used to study formation of steady spin polarization domains during quench dynamics.

Faster algorithm for turn-based stochastic games with bounded treewidth - Chatterjee, Krishnendu; Meggendorfer, Tobias; Saona Urmeneta, Raimundo J; Svoboda, Jakub (Proceedings of the 2023 Annual ACM-SIAM Symposium on Discrete Algorithms)
Turn-based stochastic games (aka simple stochastic games) are two-player zero-sum games played on directed graphs with probabilistic transitions. The goal of player-max is to maximize the probability to reach a target state against the adversarial player-min. These games lie in NP ∩ coNP and are among the rare combinatorial problems that belong to this complexity class for which the existence of polynomial-time algorithm is a major open question. While randomized sub-exponential time algorithm exists, all known deterministic algorithms require exponential time in the worst-case. An important open question has been whether faster algorithms can be obtained parametrized by the treewidth of the game graph. Even deterministic sub-exponential time algorithm for constant treewidth turn-based stochastic games has remain elusive. In this work our main result is a deterministic algorithm to solve turn-based stochastic games that, given a game with n states, treewidth at most t, and the bit-complexity of the probabilistic transition function log D, has running time O ((tn2 log D)t log n). In particular, our algorithm is quasi-polynomial time for games with constant or poly-logarithmic treewidth.

Molecular Cloning Using In Vivo DNA Assembly - Arroyo-Urea, Sandra; Watson, Jake; García-Nafría, Javier (DNA Manipulation and Analysis)
Here we describe the in vivo DNA assembly approach, where molecular cloning procedures are performed using an E. coli recA-independent recombination pathway, which assembles linear fragments of DNA with short homologous termini. This pathway is present in all standard laboratory E. coli strains and, by bypassing the need for in vitro DNA assembly, allows simplified molecular cloning to be performed without the plasmid instability issues associated with specialized recombination-cloning bacterial strains. The methodology requires specific primer design and can perform all standard plasmid modifications (insertions, deletions, mutagenesis, and sub-cloning) in a rapid, simple, and cost-efficient manner, as it does not require commercial kits or specialized bacterial strains. Additionally, this approach can be used to perform complex procedures such as multiple modifications to a plasmid, as up to 6 linear fragments can be assembled in vivo by this recombination pathway. Procedures generally require less than 3 h, involving PCR amplification, DpnI digestion of template DNA, and transformation, upon which circular plasmids are assembled. In this chapter we describe the requirements, procedure, and potential pitfalls when using this technique, as well as protocol variations to overcome the most common issues.

Fast and scalable channels in Kotlin Coroutines - Koval, Nikita; Alistarh, Dan-Adrian; Elizarov, Roman (Proceedings of the ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming)
Asynchronous programming has gained significant popularity over the last decade: support for this programming pattern is available in many popular languages via libraries and native language implementations, typically in the form of coroutines or the async/await construct. Instead of programming via shared memory, this concept assumes implicit synchronization through message passing. The key data structure enabling such communication is the rendezvous channel. Roughly, a rendezvous channel is a blocking queue of size zero, so both send(e) and receive() operations wait for each other, performing a rendezvous when they meet. To optimize the message passing pattern, channels are usually equipped with a fixed-size buffer, so sends do not suspend and put elements into the buffer until its capacity is exceeded. This primitive is known as a buffered channel. This paper presents a fast and scalable algorithm for both rendezvous and buffered channels. Similarly to modern queues, our solution is based on an infinite array with two positional counters for send(e) and receive() operations, leveraging the unconditional Fetch-And-Add instruction to update them. Yet, the algorithm requires non-trivial modifications of this classic pattern, in order to support the full channel semantics, such as buffering and cancellation of waiting requests. We compare the performance of our solution to that of the Kotlin implementation, as well as against other academic proposals, showing up to 9.8× speedup. To showcase its expressiveness and performance, we also integrated the proposed algorithm into the standard Kotlin Coroutines library, replacing the previous channel implementations.

Unexpected scaling in path copying trees - Aksenov, Vitaly; Brown, Trevor A; Fedorov, Alexander; Kokorin, Ilya (Proceedings of the ACM SIGPLAN Symposium on Principles and Practice of Parallel Programming)
Although a wide variety of handcrafted concurrent data structures have been proposed, there is considerable interest in universal approaches (Universal Constructions or UCs) for building concurrent data structures. UCs (semi-)automatically convert a sequential data structure into a concurrent one. The simplest approach uses locks [3, 6] that protect a sequential data structure and allow only one process to access it at a time. However, the resulting data structure is blocking. Most work on UCs instead focuses on obtaining non-blocking progress guarantees such as obstruction-freedom, lock-freedom or wait-freedom. Many non-blocking UCs have appeared. Key examples include the seminal wait-free UC [2] by Herlihy, a NUMA-aware UC [10] by Yi et al., and an efficient UC for large objects [1] by Fatourou et al.

Dynamic maintenance of monotone dynamic programs and applications - Henzinger, Monika H; Neumann, Stefan; Räcke, Harald; Schmid, Stefan (40th International Symposium on Theoretical Aspects of Computer Science)
Dynamic programming (DP) is one of the fundamental paradigms in algorithm design. However, many DP algorithms have to fill in large DP tables, represented by two-dimensional arrays, which causes at least quadratic running times and space usages. This has led to the development of improved algorithms for special cases when the DPs satisfy additional properties like, e.g., the Monge property or total monotonicity. In this paper, we consider a new condition which assumes (among some other technical assumptions) that the rows of the DP table are monotone. Under this assumption, we introduce a novel data structure for computing (1 + ϵ)-approximate DP solutions in near-linear time and space in the static setting, and with polylogarithmic update times when the DP entries change dynamically. To the best of our knowledge, our new condition is incomparable to previous conditions and is the first which allows to derive dynamic algorithms based on existing DPs. Instead of using two-dimensional arrays to store the DP tables, we store the rows of the DP tables using monotone piecewise constant functions. This allows us to store length-n DP table rows with entries in [0, W] using only polylog(n, W) bits, and to perform operations, such as (min, +)-convolution or rounding, on these functions in polylogarithmic time. We further present several applications of our data structure. For bicriteria versions of k-balanced graph partitioning and simultaneous source location, we obtain the first dynamic algorithms with subpolynomial update times, as well as the first static algorithms using only near-linear time and space. Additionally, we obtain the currently fastest algorithm for fully dynamic knapsack.

To flee, or not to flee? Using innate defensive behaviours to investigate rapid perceptual decision-making through subcortical circuits in mouse models of autism - Burnett, Laura
The process of detecting and evaluating sensory information to guide behaviour is termed perceptual decision-making (PDM), and is critical for the ability of an organism to interact with its external world. Individuals with autism, a neurodevelopmental condition primarily characterised by social and communication difficulties, frequently exhibit altered sensory processing and PDM difficulties are widely reported. Recent technological advancements have pushed forward our understanding of the genetic changes accompanying this condition, however our understanding of how these mutations affect the function of specific neuronal circuits and bring about the corresponding behavioural changes remains limited. Here, we use an innate PDM task, the looming avoidance response (LAR) paradigm, to identify a convergent behavioural abnormality across three molecularly distinct genetic mouse models of autism (Cul3, Setd5 and Ptchd1). Although mutant mice can rapidly detect threatening visual stimuli, their responses are consistently delayed, requiring longer to initiate an appropriate response than their wild-type siblings. Mutant animals show abnormal adaptation in both their stimulus- evoked escape responses and exploratory dynamics following repeated stimulus presentations. Similarly delayed behavioural responses are observed in wild-type animals when faced with more ambiguous threats, suggesting the mutant phenotype could arise from a dysfunction in the flexible control of this PDM process. Our knowledge of the core neuronal circuitry mediating the LAR facilitated a detailed dissection of the neuronal mechanisms underlying the behavioural impairment. In vivo extracellular recording revealed that visual responses were unaffected within a key brain region for the rapid processing of visual threats, the superior colliculus (SC), indicating that the behavioural delay was unlikely to originate from sensory impairments. Delayed behavioural responses were recapitulated in the Setd5 model following optogenetic stimulation of the excitatory output neurons of the SC, which are known to mediate escape initiation through the activation of cells in the underlying dorsal periaqueductal grey (dPAG). In vitro patch-clamp recordings of dPAG cells uncovered a stark hypoexcitability phenotype in two out of the three genetic models investigated (Setd5 and Ptchd1), that in Setd5, is mediated by the misregulation of voltage-gated potassium channels. Overall, our results show that the ability to use visual information to drive efficient escape responses is impaired in three diverse genetic mouse models of autism and that, in one of the models studied, this behavioural delay likely originates from differences in the intrinsic excitability of a key subcortical node, the dPAG. Furthermore, this work showcases the use of an innate behavioural paradigm to mechanistically dissect PDM processes in autism.

Bubaak: Runtime monitoring of program verifiers - Chalupa, Marek; Henzinger, Thomas A (Tools and Algorithms for the Construction and Analysis of Systems)
The main idea behind BUBAAK is to run multiple program analyses in parallel and use runtime monitoring and enforcement to observe and control their progress in real time. The analyses send information about (un)explored states of the program and discovered invariants to a monitor. The monitor processes the received data and can force an analysis to stop the search of certain program parts (which have already been analyzed by other analyses), or to make it utilize a program invariant found by another analysis. At SV-COMP 2023, the implementation of data exchange between the monitor and the analyses was not yet completed, which is why BUBAAK only ran several analyses in parallel, without any coordination. Still, BUBAAK won the meta-category FalsificationOverall and placed very well in several other (sub)-categories of the competition.

Area formula for spherical polygons via prequantization - Chern, Albert; Ishida, Sadashige (arXiv)
We present a formula for the signed area of a spherical polygon via prequantization. In contrast to the traditional formula based on the Gauss-Bonnet theorem that requires measuring angles, the new formula mimics Green's theorem and is applicable to a wider range of degenerate spherical curves and polygons.

Vamos: Middleware for best-effort third-party monitoring - Chalupa, Marek; Mühlböck, Fabian; Muroya Lei, Stefanie; Henzinger, Thomas A (Fundamental Approaches to Software Engineering)
As the complexity and criticality of software increase every year, so does the importance of run-time monitoring. Third-party monitoring, with limited knowledge of the monitored software, and best-effort monitoring, which keeps pace with the monitored software, are especially valuable, yet underexplored areas of run-time monitoring. Most existing monitoring frameworks do not support their combination because they either require access to the monitored code for instrumentation purposes or the processing of all observed events, or both. We present a middleware framework, VAMOS, for the run-time monitoring of software which is explicitly designed to support third-party and best-effort scenarios. The design goals of VAMOS are (i) efficiency (keeping pace at low overhead), (ii) flexibility (the ability to monitor black-box code through a variety of different event channels, and the connectability to monitors written in different specification languages), and (iii) ease-of-use. To achieve its goals, VAMOS combines aspects of event broker and event recognition systems with aspects of stream processing systems. We implemented a prototype toolchain for VAMOS and conducted experiments including a case study of monitoring for data races. The results indicate that VAMOS enables writing useful yet efficient monitors, is compatible with a variety of event sources and monitor specifications, and simplifies key aspects of setting up a monitoring system from scratch.

VAMOS: Middleware for Best-Effort Third-Party Monitoring - Chalupa, Marek; Mühlböck, Fabian; Muroya Lei, Stefanie; Henzinger, Thomas A
As the complexity and criticality of software increase every year, so does the importance of run-time monitoring. Third-party monitoring, with limited knowledge of the monitored software, and best-effort monitoring, which keeps pace with the monitored software, are especially valuable, yet underexplored areas of run-time monitoring. Most existing monitoring frameworks do not support their combination because they either require access to the monitored code for instrumentation purposes or the processing of all observed events, or both. We present a middleware framework, VAMOS, for the run-time monitoring of software which is explicitly designed to support third-party and best-effort scenarios. The design goals of VAMOS are (i) efficiency (keeping pace at low overhead), (ii) flexibility (the ability to monitor black-box code through a variety of different event channels, and the connectability to monitors written in different specification languages), and (iii) ease-of-use. To achieve its goals, VAMOS combines aspects of event broker and event recognition systems with aspects of stream processing systems. We implemented a prototype toolchain for VAMOS and conducted experiments including a case study of monitoring for data races. The results indicate that VAMOS enables writing useful yet efficient monitors, is compatible with a variety of event sources and monitor specifications, and simplifies key aspects of setting up a monitoring system from scratch.
Keywords: runtime monitoring; best effort; third party

Altered childhood brain development in autism and epilepsy - Currin, Christopher; Beyer, Chad (Encyclopedia of Child and Adolescent Health)
Autism spectrum disorder (ASD) and epilepsy are frequently comorbid neurodevelopmental disorders. Extensive research has demonstrated shared pathological pathways, etiologies, and phenotypes. Many risk factors for these disorders, like genetic mutations and environmental pressures, are linked to changes in childhood brain development, which is a critical period for their manifestation. Decades of research have yielded many signatures for ASD and epilepsy, some shared and others unique or opposing. The anatomical, physiological, and behavioral correlates of these disorders are discussed in this chapter in the context of understanding shared pathological pathways. We end with important takeaways on the presentation, prevention, intervention, and policy changes for ASD and epilepsy. This chapter aims to explore the complexity of these disorders, both in etiology and phenotypes, with the further goal of appreciating the expanse of unknowns still to explore about the brain.

Dynamic chromatin regulatory programs during embryogenesis of hexaploid wheat - Zhao, Long; Yang, Yiman; Chen, Jinchao; Lin, Xuelei; Zhang, Hao; Wang, Hao; Wang, Hongzhe; Bie, Xiaomin; Jiang, Jiafu; Feng, Xiaoqi; Fu, Xiangdong; Zhang, Xiansheng; et al. (Genome Biology)
Background: Plant and animal embryogenesis have conserved and distinct features. Cell fate transitions occur during embryogenesis in both plants and animals. The epigenomic processes regulating plant embryogenesis remain largely elusive. Results: Here, we elucidate chromatin and transcriptomic dynamics during embryogenesis of the most cultivated crop, hexaploid wheat. Time-series analysis reveals stage-specific and proximal–distal distinct chromatin accessibility and dynamics concordant with transcriptome changes. Following fertilization, the remodeling kinetics of H3K4me3, H3K27ac, and H3K27me3 differ from that in mammals, highlighting considerable species-specific epigenomic dynamics during zygotic genome activation. Polycomb repressive complex 2 (PRC2)-mediated H3K27me3 deposition is important for embryo establishment. Later H3K27ac, H3K27me3, and chromatin accessibility undergo dramatic remodeling to establish a permissive chromatin environment facilitating the access of transcription factors to cis-elements for fate patterning. Embryonic maturation is characterized by increasing H3K27me3 and decreasing chromatin accessibility, which likely participates in restricting totipotency while preventing extensive organogenesis. Finally, epigenomic signatures are correlated with biased expression among homeolog triads and divergent expression after polyploidization, revealing an epigenomic contributor to subgenome diversification in an allohexaploid genome. Conclusions: Collectively, we present an invaluable resource for comparative and mechanistic analysis of the epigenomic regulation of crop embryogenesis.

Hausdorff and Gromov-Hausdorff stable subsets of the medial axis - Lieutier, André; Wintraecken, Mathijs (Proceedings of the 55th Annual ACM Symposium on Theory of Computing)
In this paper we introduce a pruning of the medial axis called the (λ,α)-medial axis (axλα). We prove that the (λ,α)-medial axis of a set K is stable in a Gromov-Hausdorff sense under weak assumptions. More formally we prove that if K and K′ are close in the Hausdorff (dH) sense then the (λ,α)-medial axes of K and K′ are close as metric spaces, that is the Gromov-Hausdorff distance (dGH) between the two is 1/4-Hölder in the sense that dGH (axλα(K),axλα(K′)) ≲ dH(K,K′)1/4. The Hausdorff distance between the two medial axes is also bounded, by dH (axλα(K),λα(K′)) ≲ dH(K,K′)1/2. These quantified stability results provide guarantees for practical computations of medial axes from approximations. Moreover, they provide key ingredients for studying the computability of the medial axis in the context of computable analysis.

CrAM: A Compression-Aware Minimizer - Peste, Elena-Alexandra; Vladu, Adrian; Kurtic, Eldar; Lampert, Christoph; Alistarh, Dan-Adrian (11th International Conference on Learning Representations)
Deep neural networks (DNNs) often have to be compressed, via pruning and/or quantization, before they can be deployed in practical settings. In this work we propose a new compression-aware minimizer dubbed CrAM that modifies the optimization step in a principled way, in order to produce models whose local loss behavior is stable under compression operations such as pruning. Thus, dense models trained via CrAM should be compressible post-training, in a single step, without significant accuracy loss. Experimental results on standard benchmarks, such as residual networks for ImageNet classification and BERT models for language modelling, show that CrAM produces dense models that can be more accurate than the standard SGD/Adam-based baselines, but which are stable under weight pruning: specifically, we can prune models in one-shot to 70-80% sparsity with almost no accuracy loss, and to 90% with reasonable (∼1%) accuracy loss, which is competitive with gradual compression methods. Additionally, CrAM can produce sparse models which perform well for transfer learning, and it also works for semi-structured 2:4 pruning patterns supported by GPU hardware. The code for reproducing the results is available at this https URL .

Certifying giant nonprimes - Hoffmann, Charlotte; Hubáček, Pavel; Kamath, Chethan; Pietrzak, Krzysztof Z (Public-Key Cryptography - PKC 2023)
GIMPS and PrimeGrid are large-scale distributed projects dedicated to searching giant prime numbers, usually of special forms like Mersenne and Proth primes. The numbers in the current search-space are millions of digits large and the participating volunteers need to run resource-consuming primality tests. Once a candidate prime N has been found, the only way for another party to independently verify the primality of N used to be by repeating the expensive primality test. To avoid the need for second recomputation of each primality test, these projects have recently adopted certifying mechanisms that enable efficient verification of performed tests. However, the mechanisms presently in place only detect benign errors and there is no guarantee against adversarial behavior: a malicious volunteer can mislead the project to reject a giant prime as being non-prime. In this paper, we propose a practical, cryptographically-sound mechanism for certifying the non-primality of Proth numbers. That is, a volunteer can – parallel to running the primality test for N – generate an efficiently verifiable proof at a little extra cost certifying that N is not prime. The interactive protocol has statistical soundness and can be made non-interactive using the Fiat-Shamir heuristic. Our approach is based on a cryptographic primitive called Proof of Exponentiation (PoE) which, for a group G, certifies that a tuple (x,y,T)∈G2×N satisfies x2T=y (Pietrzak, ITCS 2019 and Wesolowski, J. Cryptol. 2020). In particular, we show how to adapt Pietrzak’s PoE at a moderate additional cost to make it a cryptographically-sound certificate of non-primality.

A learner-verifier framework for neural network controllers and certificates of stochastic systems - Chatterjee, Krishnendu; Henzinger, Thomas A; Lechner, Mathias; Zikelic, Dorde (Tools and Algorithms for the Construction and Analysis of Systems)
Reinforcement learning has received much attention for learning controllers of deterministic systems. We consider a learner-verifier framework for stochastic control systems and survey recent methods that formally guarantee a conjunction of reachability and safety properties. Given a property and a lower bound on the probability of the property being satisfied, our framework jointly learns a control policy and a formal certificate to ensure the satisfaction of the property with a desired probability threshold. Both the control policy and the formal certificate are continuous functions from states to reals, which are learned as parameterized neural networks. While in the deterministic case, the certificates are invariant and barrier functions for safety, or Lyapunov and ranking functions for liveness, in the stochastic case the certificates are supermartingales. For certificate verification, we use interval arithmetic abstract interpretation to bound the expected values of neural network functions.

Computing adequately permissive assumptions for synthesis - Anand, Ashwani; Mallik, Kaushik; Nayak, Satya Prakash; Schmuck, Anne Kathrin (TACAS 2023: Tools and Algorithms for the Construction and Analysis of Systems)
We automatically compute a new class of environment assumptions in two-player turn-based finite graph games which characterize an “adequate cooperation” needed from the environment to allow the system player to win. Given an ω-regular winning condition Φ for the system player, we compute an ω-regular assumption Ψ for the environment player, such that (i) every environment strategy compliant with Ψ allows the system to fulfill Φ (sufficiency), (ii) Ψ can be fulfilled by the environment for every strategy of the system (implementability), and (iii) Ψ does not prevent any cooperative strategy choice (permissiveness). For parity games, which are canonical representations of ω-regular games, we present a polynomial-time algorithm for the symbolic computation of adequately permissive assumptions and show that our algorithm runs faster and produces better assumptions than existing approaches—both theoretically and empirically. To the best of our knowledge, for ω -regular games, we provide the first algorithm to compute sufficient and implementable environment assumptions that are also permissive.

Neural control of optic flow-based navigation in Drosophila melanogaster - Pokusaeva, Victoria
During navigation, animals can infer the structure of the environment by computing the optic flow cues elicited by their own movements, and subsequently use this information to instruct proper locomotor actions. These computations require a panoramic assessment of the visual environment in order to disambiguate similar sensory experiences that may require distinct behavioral responses. The estimation of the global motion patterns is therefore essential for successful navigation. Yet, our understanding of the algorithms and implementations that enable coherent panoramic visual perception remains scarce. Here I pursue this problem by dissecting the functional aspects of interneuronal communication in the lobula plate tangential cell network in Drosophila melanogaster. The results presented in the thesis demonstrate that the basis for effective interpretation of the optic flow in this circuit are stereotyped synaptic connections that mediate the formation of distinct subnetworks, each extracting a particular pattern of global motion. Firstly, I show that gap junctions are essential for a correct interpretation of binocular motion cues by horizontal motion-sensitive cells. HS cells form electrical synapses with contralateral H2 neurons that are involved in detecting yaw rotation and translation. I developed an FlpStop-mediated mutant of a gap junction protein ShakB that disrupts these electrical synapses. While the loss of electrical synapses does not affect the tuning of the direction selectivity in HS neurons, it severely alters their sensitivity to horizontal motion in the contralateral side. These physiological changes result in an inappropriate integration of binocular motion cues in walking animals. While wild-type flies form a binocular perception of visual motion by non-linear integration of monocular optic flow cues, the mutant flies sum the monocular inputs linearly. These results indicate that rather than averaging signals in neighboring neurons, gap-junctions operate in conjunction with chemical synapses to mediate complex non-linear optic flow computations. Secondly, I show that stochastic manipulation of neuronal activity in the lobula plate tangential cell network is a powerful approach to study the neuronal implementation of optic flow-based navigation in flies. Tangential neurons form multiple subnetworks, each mediating course-stabilizing response to a particular global pattern of visual motion. Application of genetic mosaic techniques can provide sparse optogenetic activation of HS cells in numerous combinations. These distinct combinations of activated neurons drive an array of distinct behavioral responses, providing important insights into how visuomotor transformation is performed in the lobula plate tangential cell network. This approach can be complemented by stochastic silencing of tangential neurons, enabling direct assessment of the functional role of individual tangential neurons in the processing of specific visual motion patterns. Taken together, the findings presented in this thesis suggest that establishing specific activity patterns of tangential cells via stereotyped synaptic connectivity is a key to efficient optic flow-based navigation in Drosophila melanogaster.